toner
By using silicon polymer composites with specific metal atoms and silicon polymer composite surfaces in electro-optical image formation technology, the problem of image quality degradation in high temperature and high humidity environments is solved, and efficient charge injection and image stability are achieved.
Patent Information
- Application Number
- JP2024150913
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-19
- Filing Date
- 2024-09-02
- Publication Date
- 2025-04-01
AI Technical Summary
In the accelerated printing process, existing electro-optical image formation technology is prone to atomization (fog) problems, especially in high temperature and high humidity environments, resulting in a decline in image quality.
Using a silicon polymer composite with a surface of a silicon polymer composite, the surface exposure ratio and absolute number of metal atoms are controlled to achieve efficient charge injection and retention by including specific metal atoms in the silicon polymer composite, such as metal atoms from Group 3 to 13, and measuring their atomic ratio by X-ray electron spectroscopy.
It realizes the image quality in high temperature and high humidity environments, avoids atomization problems, and improves the charge injection performance and image stability during printing.
Smart Images

Figure 2025044147000005 
Figure 2025044147000006 
Figure 2025044147000001
Abstract
Description
[Technical field]
[0001] This disclosure relates to toners for use in electrophotography. [Background technology]
[0002] In recent years, the fields in which electrophotographic image formation is used have become more diverse, ranging from printers and copiers to commercial printing machines. Accordingly, the demand for higher image quality, higher speed, and higher durability for electrophotography has been increasing. In addition, as the performance of electrophotography has improved, it has become more widespread worldwide and is used in a variety of environments, both indoors and outdoors. There is a demand for it to be able to consistently provide high-quality images while adapting to such a variety of environments. As the speed increases, the contact time between the toner and the charging member tends to become shorter, and the time required for the toner to be charged becomes shorter, which causes the problem of fog generation described below to become more pronounced.
[0003] First, the process by which fogging occurs will be described. After being conveyed onto a toner carrier, the toner is frictionally charged by rubbing against a charge-imparting member. Thereafter, the toner is caused to fly from the toner carrier to an electrostatic latent image on an electrostatic latent image carrier (hereinafter referred to as an electrophotographic photoreceptor or photoreceptor) by electrostatic force, forming an image. If the toner is not sufficiently and uniformly charged by friction, there will be a large number of toners with low charge levels or toners with inverted absolute values of charge, which tends to result in a broad charge distribution. As a result, these toners fly to non-image areas, causing image defects (hereinafter referred to as fogging) in which non-printed areas are colored. When the speed of the printing process described above is increased, charging abnormalities such as the generation of toner with a low charge amount or the generation of toner with an inverted absolute value of the charge are more likely to occur, and fogging is more likely to occur.
[0004] In order to improve such fogging, studies are being conducted on the existence of conductive fine particles on the toner surface to promote electrostatic induction and dielectric polarization in the injection charging process in addition to the frictional charging in the conventional frictional charging process, thereby improving the charge rise property. Here, the injection charging process is a process in which the toner is charged by injecting charge due to the potential difference between the toner and the charging member. In these processes, the existence of conductive fine particles on the toner surface can increase the number of charging sites on the toner surface. Therefore, even if the charge imparting time is shortened by increasing the speed, the toner can be sufficiently charged, so that the occurrence of fogging can be suppressed under normal temperature and humidity environments.
[0005] However, the suppression of fogging by adding conductive fine particles to the surface is difficult to obtain in high temperature and high humidity environments. This is because the conductive fine particles act as moisture adsorption sites, so if the amount of conductive fine particles on the toner surface is increased to accommodate higher speeds, moisture is more likely to be adsorbed to the toner surface. This effect is particularly noticeable when the image forming apparatus is started after the toner has been left in an environment with a high absolute moisture content for a long period of time.
[0006] In response to these problems, Patent Document 1 discloses a toner in which silica-titania composite particles having a core-shell structure with controlled silica content and zeta potential are produced by a gas phase method and added to the surface of the toner particles to improve charging stability and suppress fogging. Patent Document 2 discloses a toner that can impart stable charging characteristics and suppress fogging throughout image durability by introducing weakly negative aluminum (alumina) or titanium into the -Si-Si- bond of silica particles, which are known as strongly negative materials, as an external additive to the toner.
[0007] Patent Document 3 discloses a toner in which the surface of a toner particle is provided with a convex made of an organosilicon polymer, and a polyvalent acid metal salt is provided on the surface of the convex, thereby realizing an injection charging process and suppressing changes in charge amount due to the environment. By using the injection charging process, a conductive path is provided in the toner or between the toner particles, so that the entire toner can be uniformly and quickly charged, not just the part in contact with the charging member. Therefore, even if the amount of polyvalent acid metal salt present on the surface is small, a good charge rise can be achieved. In addition, with injection charging, the charge amount can be controlled arbitrarily by changing the potential difference, so it is less susceptible to the influence of humidity. Therefore, it is possible to suppress changes in charge amount due to the environment and suppress fogging. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2011-118210 A [Patent Document 2] JP 2007-017486 A [Patent Document 3] Patent Publication No. 2021-021791 Summary of the Invention [Problem to be solved by the invention]
[0009] The toner described in the above Patent Document 1 has a core-shell structure in which titania is covered with silica, thereby controlling the zeta potential, improving the maintenance and rise of charge, and suppressing fogging. However, the toner described in the above Patent Document 1 contains a large amount of titania, which makes it easy to generate excessive conductive paths, and it is difficult to completely control the core-shell structure of the composite oxide produced by the gas phase method. Therefore, charge may leak through the partially exposed titania, resulting in a decrease in the charge rise property.
[0010] The toner described in the above Patent Document 2 achieves charging stability without increasing the number of moisture adsorption sites by doping silica particles with a small amount of titanium. However, the complex oxide generated by the vapor phase oxidation of a metal halide compound cannot control the location of titanium, and the amount of titanium exposed on the toner surface is extremely large. Therefore, the problem of fogging caused by moisture adsorption to the titanium on the surface under high temperature and high humidity conditions remains. In addition, the toner described in Patent Document 2 contains only a very small amount of titanium and the dispersion state is not controlled, so there are not enough charging sites for triboelectric charging and a sufficient amount of charge cannot be obtained. Therefore, it is insufficient to eliminate fogging in the high-speed printing process that is required in recent years.
[0011] The toner described in Patent Document 3 achieves charge rise performance that is less dependent on the environment by utilizing an injection charging process. On the other hand, due to the uneven distribution of metal atoms derived from polyvalent acid metal salts on the outermost surface of the toner, there are many moisture adsorption sites, and the exposed polyvalent acid metal salts act as charge leakage points. Therefore, the charge leakage is not sufficiently suppressed to meet the increased process speed under high temperature and high humidity conditions, and in particular, sufficient charging properties may not be obtained to suppress fogging under severe high temperature and high humidity conditions.
[0012] The present disclosure provides a toner that enables precise charge control and can eliminate fogging regardless of the environment, including harsh high-temperature and high-humidity environments, even when the printing process is accelerated. [Means for solving the problem]
[0013] The present disclosure provides a toner having toner particles having a binder resin, The toner particles have a toner base particle and a silicon polymer composite present on a surface of the toner base particle, The silicon polymer composite comprises: a silicon polymer; At least one specific metal atom selected from the group consisting of metal atoms included in Groups 3 to 13; Contains a ratio of the number of specific metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, phosphorus atoms and the specific metal atoms, which is obtained by X-ray photoelectron spectroscopy analysis of the toner, is defined as ME, and a ratio of the number of silicon atoms is defined as SiE, In an EDS mapping image of constituent elements of a cross section of the toner, which is obtained by analyzing the cross section of the toner observed with a transmission electron microscope with an energy dispersive X-ray spectrometer, the ratio of the number of atoms of the specific metal atoms to the sum of the numbers of silicon atoms and the specific metal atoms in a region outside the contour of the toner mother particle is defined as MX, The toner relates to the above-mentioned ME, SiE, and MX, which satisfy the following formulae (1) and (2). 0.50 ≦(ME / SiE) / MX ≦ 2.50 (1) 5.0×10 -3 ≦MX ≦6.0×10 -2 (2) Effect of the Invention
[0014] According to the present disclosure, a toner can be provided that enables precise charge control by achieving a high level of both charge rise and suppression of charge leakage due to moisture adsorption, and can eliminate fogging regardless of the environment, including harsh high-temperature and high-humidity environments, even when the printing process is accelerated. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is an example of a STEM image of the toner used in the present example. [Diagram 2] FIG. 2 is a schematic diagram of a cross section of a toner used in the present example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower limit and the upper limit, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper limit and the lower limit of each numerical range can be arbitrarily combined. In addition, in the present disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ. Note that when XX is a group, multiple XXs may be selected, and the same applies to YY and ZZ.
[0017] In the toner charging process in triboelectric charging, when the printing process is accelerated, the friction between the charging member or carrier (hereinafter collectively referred to as the charging member) and the toner is insufficient, resulting in the presence of a large amount of toner with a low charge amount or toner with an inverted absolute value of the charge, and the distribution of the charge of the toner may become broad. This effect is particularly noticeable after the toner is left in a high-temperature, high-humidity environment for a long period of time. In order to suppress the generation of toner with a low charge amount or toner with an inverted absolute value of the charge regardless of the environment, it is effective to control the charge amount to an arbitrary amount by injecting charge from the charging member into the toner.
[0018] In this case, when the polyvalent metal salt is unevenly distributed on the outermost surface of the toner as in Patent Document 3 and injection charging is performed, the charge may leak through the exposed polyvalent metal salt. Furthermore, the charge may leak due to moisture adsorbed to the polyvalent metal salt on the surface, and sufficient charge rise property for eliminating fogging may not be obtained. Therefore, in order to increase the charge rise property in the high-speed printing process under a high-temperature and high-humidity environment, it is necessary to increase the charge injection property while suppressing the charge leakage through the polyvalent metal salt and adsorbed moisture to increase the charge retention property.
[0019] As a result of extensive research, the present inventors have found that a toner having the following composition can eliminate fogging even when the printing process is speeded up in any environment, including harsh high-temperature and high-humidity environments.
[0020] That is, the present disclosure provides a toner having toner particles having a binder resin, The toner particles have a toner base particle and a silicon polymer composite present on a surface of the toner base particle, The silicon polymer composite comprises: a silicon polymer; At least one specific metal atom selected from the group consisting of metal atoms included in Groups 3 to 13; Contains a ratio of the number of specific metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, phosphorus atoms and the specific metal atoms, which is obtained by X-ray photoelectron spectroscopy analysis of the toner, is defined as ME, and a ratio of the number of silicon atoms is defined as SiE, In an EDS mapping image of constituent elements of a cross section of the toner, which is obtained by analyzing the cross section of the toner observed with a transmission electron microscope with an energy dispersive X-ray spectrometer, the ratio of the number of atoms of the specific metal atoms to the sum of the numbers of silicon atoms and the specific metal atoms in a region outside the contour of the toner mother particle is defined as MX, The toner relates to the above-mentioned ME, SiE, and MX, which satisfy the following formulae (1) and (2). 0.50 ≦(ME / SiE) / MX ≦ 2.50 (1) 5.0×10 -3 ≦MX ≦6.0×10 -2 (2)
[0021] The present inventors considered that the above-mentioned problems could be solved if the exposure of metal atoms and the adsorption of moisture to conductive fine particles could be suppressed even when metal atoms are present near the toner surface to improve the charge rise property. Furthermore, they considered that it would be effective to cover the metal atoms with a highly insulating material such as a silicon polymer in order to simultaneously suppress the adsorption of moisture and the leakage of charge. Specifically, the inventors considered it necessary to form a composite of metal atoms and silicon polymers, as well as to control the surface-exposed ratio and absolute amount of metal atoms.
[0022] The present inventors consider the mechanism by which the effects of the present disclosure are manifested as follows. First, the toner of the present disclosure is characterized in that a silicon polymer composite is formed from a silicon polymer and at least one specific metal atom selected from the group consisting of metal atoms included in groups 3 to 13. When this type of configuration is adopted, the metal atom is covered with the silicon polymer, and moisture adsorption to the metal atom is suppressed, thereby making it possible to suppress the occurrence of fogging in a high-temperature, high-humidity environment.
[0023] In addition, compared with the case where the particles containing metal atoms and the silicon polymer particles exist alone, the silicon polymer and the metal are composited, and the electrostatic induction of the metal promotes the dielectric polarization of the adjacent dielectric, the silicon polymer.As a result, even if the surface exposure ratio or absolute amount of the metal atoms is small, it is believed that sufficient charge rising property can be exhibited.
[0024] The silicon polymer composite in the present disclosure has a structure in which a silicon polymer and a compound containing the specific metal atom described above are adjacent to each other. In particular, compounds composed of metal atoms included in groups 3 to 13 have low water absorption and therefore high charge stability in high temperature and high humidity environments compared to compounds containing only metal atoms of groups 1 and 2. Furthermore, metal atoms included in groups 3 to 13 have a valence of 2 or more, and form a crosslinked structure with oxygen atoms of the silicon polymer, thereby forming a strong silicon polymer. Therefore, high charge stability can be maintained over a long period of time.
[0025] In addition, the silicon polymer contained in the silicon polymer composite has a siloxane bond skeleton in the molecule, so that the oxygen atom site with high electronegativity shows high affinity with metal atoms. The silicon polymer has affinity with the specific metal atom, so that the specific metal atom can be highly dispersed in the silicon polymer composite without forming a large agglomerate. Therefore, the percolation phenomenon is likely to occur, and even if the content of metal atoms is small, it is thought that a large electric dipole can be formed by the transfer of charge between metal atoms. As a result, the charge injection property is high, the charge rise is good, and the elimination of fogging can be achieved.
[0026] As described above, the toner of the present disclosure is characterized in that the specific metal atom forms a composite with the silicon polymer, and in that the location and amount of the specific metal atom are highly controlled.
[0027] In this disclosure, the ratio of the amount of specific metal atoms present in the outermost surface (ME / SiE) determined by X-ray photoelectron spectroscopy (ESCA) to the amount of specific metal atoms present in the cross section of the toner observed by a scanning transmission electron microscope (STEM) is used as an index representing the location of the specific metal atoms. MX reflects the total amount of specific metal atoms near the toner surface, and (ME / SiE) reflects the amount of specific metal atoms present at a depth of several nm from the toner surface.
[0028] That is, based on X-ray photoelectron spectroscopy using a toner sample, the ratio of the number of specific metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, phosphorus atoms and the specific metal atoms is defined as ME, and the ratio of the number of silicon atoms is defined as SiE. In addition, an EDS mapping image of the constituent elements of the toner cross section observed with a transmission electron microscope is obtained by analyzing the cross section of the toner with an energy dispersive X-ray spectrometer. In the EDS mapping image, the ratio of the number of the specific metal atoms to the total number of silicon atoms and the specific metal atoms in the region outside the contour of the toner mother particle is defined as MX. In this case, ME, SiE, and MX satisfy the following formulas (1) and (2). 0.50 ≦(ME / SiE) / MX ≦ 2.50 (1) 5.0×10 -3 ≦MX ≦6.0×10 -2 (2)
[0029] In the above formula (1), the ratio of (ME / SiE) to MX represents the ratio of the specific metal atom exposed on the surface, and the higher the value, the higher the ratio of the specific metal atom exposed on the surface. In the above formula (1), the ratio of (ME / SiE) to MX of 0.50 or more represents a state in which a very small amount of the specific metal atom is exposed on the surface of the silicon polymer composite, and excessive charge is prevented from remaining in the silicon polymer composite and causing overcharging. As a result, the occurrence of fogging caused by overcharging, which is particularly noticeable in low temperature and low humidity environments, can be suppressed. Furthermore, by making the ratio of (ME / SiE) to MX 2.50 or less, the amount of specific metal atoms exposed on the surface of the silicon polymer composite can be reduced, which in turn makes it possible to suppress charge leakage via the exposed specific metal atoms or moisture adsorbed on the specific metal atoms, thereby making it possible to suppress the occurrence of fogging in high temperature and high humidity environments.
[0030] Furthermore, when the above (1) is satisfied, it is considered that the specific metal atoms are largely encapsulated in the silicon polymer, which is a dielectric. In this case, when the specific metal atoms are electrostatically polarized by applying a bias to the toner charging member, the polarization of the dielectric adjacent to the specific metal atoms is promoted. This effect is particularly noticeable in the case of materials that are easily dielectrically polarized, such as silicon polymers.
[0031] Furthermore, encapsulating many of the specific metal atoms in the silicon polymer so as to satisfy the above (1) is also effective in increasing the dispersibility of the specific metal atoms. In this case, it is considered that the particles of the specific metal atoms are well dispersed in the silicon polymer matrix. Therefore, at a certain particle packing rate, the particles are connected to form a conductive path, and the conductivity increases rapidly, which is the so-called percolation phenomenon. Therefore, even if the toner of the present disclosure has a small content of the specific metal atoms, a large electric dipole can be formed by forming a good conductive path between the metal atoms. It is believed that the above mechanism enhances charge injection, exhibits good charge rise characteristics, and eliminates fogging regardless of the environment, including harsh high-temperature and high-humidity environments. The ratio (ME / SiE) / MX is preferably from 0.65 to 2.10, and more preferably from 0.75 to 1.90.
[0032] Furthermore, in the toner of the present disclosure, in addition to the above-mentioned exposed ratio of the specific metal atom on the surface, it is necessary to control the absolute amount of the specific metal atom using MX as an index, that is, it is necessary to satisfy the above formula (2). In the above formula (2), MX is 5.0 × 10 -3 When the MX is 6.0×10 or more, the charge injection property by the charging member is good. Therefore, a high charge rise property can be exhibited, and the occurrence of fogging in a high temperature and high humidity environment can be suppressed. -2 By satisfying the following conditions, it is possible to reduce the absolute amount of specific metal atoms exposed on the silicon polymer composite surface, which is believed to be why it is possible to suppress charge leakage via the exposed metal atoms or moisture adsorbed on the metal atoms, thereby suppressing the occurrence of fogging in high temperature and high humidity environments.
[0033] To sum up the above mechanism, it is believed that by encapsulating a small amount of specific metal atoms near the toner surface in the silicon polymer within the above specific range, moisture adsorption and charge leakage via metal atoms can be suppressed. Furthermore, it is believed that high charge injection properties can be achieved by dispersing metal atoms in the silicon polymer, which has a high polarizability among insulators. In this way, it is believed that both the effects of leakage suppression and charge rise are obtained.
[0034] In addition, the present disclosure is the first to realize a composition in which a small amount of specific metal atom and silicon polymer are present on the toner surface as a composite, and the location and amount of the specific metal atom are highly controlled. This characteristic makes it possible to suppress fogging even when the printing process is speeded up in any environment, including harsh high-temperature and high-humidity environments.
[0035] Methods for obtaining a toner that satisfies the above formulas (1) and (2) include a method in which a metal compound serving as a metal source is reacted with a silicon compound in an aqueous medium in which toner base particles are dispersed to obtain a silicon polymer composite, and a method in which a silicon polymer composite is attached to toner particles by mechanical external force in a dry or wet manner. The detailed method will be described later.
[0036] In addition to the above configuration, the toner will be described below. <Surface condition of toner particles> The specific metal atom may be at least one metal element selected from the group consisting of metal elements included in Groups 3 to 13. Specific examples of the specific metal atom include at least one selected from the group consisting of titanium (Group 4, electronegativity: 1.54), zirconium (Group 4, electronegativity: 1.33), aluminum (Group 13, electronegativity: 1.61), zinc (Group 12, electronegativity: 1.65), indium (Group 13, electronegativity: 1.78), hafnium (Group 4, electronegativity: 1.30), iron (Group 8, electronegativity: 1.83), copper (Group 11, electronegativity: 1.90), and silver (Group 11, electronegativity: 1.93).
[0037] The specific metal atom is selected from the group consisting of titanium, zirconium, copper and aluminum. It is preferable that the metal atom is at least one metal atom.
[0038] There is no particular limitation on the method for obtaining the above-mentioned silicon polymer composite.For example, in aqueous medium, the method of obtaining silicon polymer composite can be mentioned, or the method of obtaining silicon polymer composite by growing silicon polymer and metal salt so as to share the interface.Among them, the method of obtaining silicon polymer composite by reacting metal compound as metal source with silicon compound in aqueous medium is preferred.
[0039] The silicon polymer composite is preferably a reaction product of a metal compound and a silicon compound. As the metal source for obtaining the silicon polymer composite, any known metal compound can be used without any particular limitation, as long as it is a metal compound that reacts with an acid to give a metal salt, or a metal compound that reacts with a silicon compound to give a silicon polymer composite.
[0040] Among them, the metal compound is preferably a metal chelate, since the reaction is easily controlled and the metal compound reacts quantitatively with the acid or the silicon compound. In addition, lactate chelates such as titanium lactate and zirconium lactate are more preferable from the viewpoint of solubility in aqueous media.
[0041] Specific examples of metal compounds that can be used as metal sources include at least one selected from the group consisting of metal chelates such as titanium lactate, titanium tetraacetylacetonate, titanium lactate ammonium salt, titanium triethanolamine, zirconium lactate, zirconium lactate ammonium salt, aluminum lactate, aluminum trisacetylacetonate, and copper lactate; and metal alkoxides such as titanium tetraisopropoxide, titanium ethoxide, zirconium tetraisopropoxide, and aluminum trisisopropoxide.
[0042] The metal compound is preferably at least one selected from the group consisting of metal chelates, more preferably at least one lactic acid chelate selected from the group consisting of titanium lactate, titanium lactate ammonium salt, zirconium lactate, zirconium lactate ammonium salt, aluminum lactate, and copper lactate.
[0043] The silicon polymer can be any known silicon polymer without any particular limitations. Among them, the silicon polymer is preferably an organosilicon polymer having a structure (T3 unit structure) represented by the following formula (5). The silicon polymer composite is preferably an organosilicon polymer composite. R-SiO 3 / 2 (5)
[0044] (In formula (5), R represents an alkyl group having 1 to 6 carbon atoms (preferably 1 to 3, more preferably 1 or 2, and even more preferably 1), an alkenyl group (preferably having 1 to 6 carbon atoms, more preferably 1 to 4), an acyl group (preferably having 1 to 6 carbon atoms, more preferably 1 to 4), an aryl group (preferably having 6 to 14 carbon atoms, more preferably 6 to 10 carbon atoms), or a methacryloxyalkyl group.)
[0045] The above formula (5) indicates that the organosilicon polymer has an organic group and a silicon polymer portion. As a result, the organosilicon polymer containing the structure represented by the above formula (5) is strongly attached to the toner mother particles because the organic group has affinity with the toner mother particles, and the silicon polymer portion has affinity with the specific metal atom, forming a strong complex. In this way, the toner surface has a structure in which the silicon polymer complex is firmly attached to the toner mother particles, and therefore, higher charging stability can be maintained over long periods of time.
[0046] Furthermore, since the silicon polymer is an organosilicon polymer, the silicon that coats the specific metal atom can be easily obtained. This increases the electrical resistance of the silicon polymer, thereby preventing leakage of electric charge from the toner to the toner contact member via the silicon polymer, and further suppressing fogging.
[0047] On the other hand, organosilicon polymers have a high dielectric constant, and therefore exhibit high dielectric polarization performance induced by electrostatic polarization of specific metal atoms, allowing them to exhibit high charge build-up even in high temperature and high humidity environments, further reducing the occurrence of fogging. From the viewpoint of achieving both the above-mentioned effect and suppressing a decrease in fixation property due to high coverage of the silicon polymer composite, the content of the silicon compound is preferably 0.3 parts by mass or more and 20.0 parts by mass or less per 100.0 parts by mass of the binder resin or polymerizable monomer.
[0048] The silicon compound for obtaining the silicon polymer composite is not particularly limited. From the viewpoint of obtaining the structure represented by the above formula (5), the silicon compound is preferably an organosilicon compound. As the organosilicon compound, any known organosilicon compound can be used without any particular limitation. Among them, at least one organosilicon compound selected from the group consisting of organosilicon compounds represented by the following formula (6) is preferable. R-Si-(Ra)3···(6)
[0049] In formula (6), each Ra independently represents a halogen atom or an alkoxy group having 1 to 3 carbon atoms (preferably 1 or 2), and R represents an alkyl group having 1 to 6 carbon atoms (preferably 1 to 3, more preferably 1 or 2, and even more preferably 1), an alkenyl group (preferably having 1 to 6, more preferably 1 to 4 carbon atoms), or a aryl group (preferably having 6 to 14, and more preferably 6 It represents an aryl group (having preferably 1 to 10 carbon atoms), an acyl group (having preferably 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms), or a methacryloxyalkyl group.
[0050] Specific examples of the silane compound represented by formula (6) include trifunctional methylsilane compounds such as methyltrimethoxysilane, methyltriethoxysilane, methyldiethoxymethoxysilane, and methylethoxydimethoxysilane; trifunctional silane compounds such as ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, hexyltrimethoxysilane, and hexyltriethoxysilane; and trifunctional phenylsilane compounds such as phenyltrimethoxysilane and phenyltriethoxysilane. trifunctional vinyl silane compounds such as vinyl trimethoxy silane and vinyl triethoxy silane; trifunctional allyl silane compounds such as allyl trimethoxy silane, allyl triethoxy silane, allyl diethoxy methoxy silane and allyl ethoxy dimethoxy silane; trifunctional γ-methacryloxypropyl silane compounds such as γ-methacryloxypropyl trimethoxy silane, γ-methacryloxypropyl triethoxy silane, γ-methacryloxypropyl diethoxy methoxy silane and γ-methacryloxypropyl ethoxy dimethoxy silane; and trifunctional silane compounds such as γ-methacryloxypropyl trimethoxy silane, γ-methacryloxypropyl triethoxy silane, γ-methacryloxypropyl diethoxy methoxy silane and γ-methacryloxypropyl ethoxy dimethoxy silane.
[0051] It is preferable that MX satisfies the following formula (3). 1.0×10 -2 ≦MX ≦6.0×10 -2 (3) In the above formula (3), MX is 1.0 × 10 -2 When the amount of the specific metal atom is 1.0×10 or more, the charge injection property by the charging member is improved. Therefore, the charge rise property can be improved, and the fogging suppression effect is increased. -2 Even in the above cases, since many specific metal atoms are encapsulated in the silicon polymer, there are few moisture adsorption sites on the toner surface, and water absorption is low. Therefore, aggregation between toner particles can be suppressed, and the fluidity is improved, resulting in further improvement in solid print conformability in high temperature and high humidity environments.
[0052] Here, the solid image tracking ability refers to the continuous printing of images with a very high overall printing rate (hereinafter referred to as solid images). This refers to the density stability from the second sheet onwards when printing (hereafter referred to as solid print compatibility). In order to stabilize solid print compatibility, it is necessary to quickly supply toner to developing members such as developing rollers, so high fluidity of the toner is required. MX is preferably 1.1 x 10 -2 ≦MX ≦4.8×10 -2 It is.
[0053] In the toner, it is preferred that the silicon polymer composite is fixed to the surface of the toner base particle in a convex shape. The convex shape of the silicon polymer composite makes it easier to encapsulate specific metal atoms, and can suppress charge leakage via exposed metal atoms or moisture adsorbed to metal atoms, further increasing the effect of suppressing fogging in a high-temperature, high-humidity environment. In addition, the convex shape of the silicon polymer composite increases the area in which the specific metal atoms can exist, allowing the specific metal atoms to be well dispersed in the silicon polymer composite, optimizing the conductive path and improving the start-up properties, thereby further increasing the fogging suppression effect.
[0054] Furthermore, since the silicon polymer composite has a convex shape, the contact area between the toner and the member can be reduced compared to when the silicon polymer has a film shape. As a result, the charge leakage through the silicon polymer composite can be suppressed, and the transferability is further improved. On the other hand, when the charge is injected, the uneven parts of the toner surface mesh with each other to form a scrum structure between the toner particles. When such a structure is adopted, a good conductive path is formed between the toner particles, so that the rising property is improved and a greater fogging suppression effect can be obtained. In order to fix the silicon polymer composite in a convex shape, for example, there is a method in which the conditions for the condensation reaction of the silane coupling agent on the surface of the toner base particles are controlled while the toner base particles are dispersed in an aqueous medium.
[0055] Furthermore, the cross section of the toner observed with a transmission electron microscope is analyzed with an energy dispersive X-ray spectrometer (EDS) to obtain an EDS mapping image of the constituent elements of the cross section of the toner. In this EDS mapping image, as shown in the schematic diagram of Figure 2, an image of the toner base particle 2 and an image of the silicon polymer composite 1 are observed, and it is preferable that the image of the silicon polymer composite 1 is observed at a position in the image of the toner base particle 2 that corresponds to the surface of the toner base particle 2.
[0056] In an EDS mapping image, when a line scan is performed on an area X specified by the following method, the maximum value of the intensity count of a specific metal is defined as Mmax and the average value of the intensity count is defined as Mave. It is preferable that Mmax and Mave satisfy the following formula (4). 1.00 <Mmax / Mave<1.80 ···(4) How to identify Region X: (i) A baseline 3 is defined by connecting the end points of the interface formed by the image of the silicon polymer composite 1 and the image of the toner base particle 2 in the EDS mapping image with a straight line. The baseline 3 is a line segment. (ii) Among the perpendicular lines (lines perpendicular to the baseline) connecting the baseline and the outer surface of the image of the silicon polymer composite 1 (the surface of the silicon polymer composite opposite to the toner base particle side), a perpendicular line 5 having the maximum length is determined. The perpendicular line 5 is perpendicular line L1. At this time, the length of the perpendicular line 5 is the image height H (nm). (iii) If the width of the image of the silicon polymer composite, which is the length of the baseline, is W, then define a line segment L2 on the baseline by connecting two points on the baseline that are 0.1W inward from each end of the baseline. (iv) The area where the line segment L2 is moved parallel to the base line in the direction in which the perpendicular line L1 extends to the midpoint of the perpendicular line L1 and overlaps with the image of the silicon polymer composite is defined as "area X."
[0057] The satisfaction of formula (4), i.e., the ratio of the maximum intensity count Mmax to the average intensity count Mave, is less than 1.80, which indicates that the silicon polymer composite contains a specific metal. This means that there are few areas where the atoms are extremely unevenly distributed. In other words, it is considered that the specific metal atoms are highly dispersed in the silicon polymer composite. In this case, even if the specific metal atoms in the toner are small in amount, the above-mentioned percolation phenomenon works effectively, so that a higher injection chargeability can be exhibited. Therefore, even if the toner has a structure in which the metal atoms are covered with the silicon polymer composite to suppress moisture adsorption in a high-temperature and high-humidity environment, a sufficient charge amount can be obtained, and a greater fogging suppression effect can be obtained. The ratio Mmax / Mave is more preferably from 1.20 to 1.75, and further preferably from 1.20 to 1.60.
[0058] The silicon polymer composite has a conductivity of 1.0 x 10 -5 ~1.0×10 -2 S / m is preferable, and 1.0×10 -4 ~1.0×10 -2 It is more preferable that the ratio is S / m. The conductivity measured at a frequency of 10 kHz is 1.0 x 10 -5 When the toner regulating member has a conductivity of 1.0×10 S / m or more, the charge injection from the toner regulating member to the toner becomes easier, the injected chargeability improves, and the fogging suppression effect increases. -2 By keeping the surface roughness at S / m or less, leakage of charge to the toner carrier caused by excessive increase in conductivity can be suppressed, and as a result, fogging is improved with the improvement in charge retention. Furthermore, the transferability is improved due to the increased charge retention.
[0059] The electrical conductivity of the silicon polymer composite can be calculated by sandwiching the silicon polymer composite powder between parallel plate electrodes, applying a constant load using a torque driver, and measuring the distance between the electrodes and the resistance. The detailed measurement method will be described later. The electrical conductivity of the silicon polymer composite measured at a frequency of 10 kHz can be controlled by coating the surface of the silicon polymer composite with a highly conductive polyvalent metal salt or by increasing the resistance of the surface of the silicon polymer composite using a highly resistive silane coupling agent.
[0060] In the silicon polymer composite, at least a part of the specific metal atom and at least a part of the silicon atom are preferably bonded via an oxygen atom. Here, the bond means a covalent bond. When the specific metal element is M, the silicon polymer composite preferably has an MO-Si bond. For example, when the specific metal element is Ti, the bond is a Ti-O-Si bond.
[0061] At least a part of the metal atoms and at least a part of the silicon atoms are bonded via oxygen atoms, which increases the electrical interaction between the metal atoms and the silicon polymer, and increases the dielectric polarization of the silicon polymer induced by the electrostatic polarization of the metal atoms. Therefore, the effect of improving the start-up property by the injection charging is greatly manifested.
[0062] In addition, since at least a part of the metal atoms and at least a part of the silicon atoms are bonded to each other, the metal atoms can be prevented from forming agglomerates, and the dispersibility of the metal atoms in the silicon polymer composite is improved. Therefore, a conductive path is well formed, and high injection chargeability can be exhibited. As a result, a sufficient amount of charge can be obtained, and a greater fogging suppression effect can be obtained. The chemical bond between the metal atoms and the silicon atoms via oxygen atoms can be confirmed by confirming a peak belonging to the MO-Si stretching vibration in the spectrum obtained by infrared spectroscopy. More specifically, this will be described later.
[0063] The silicon polymer composite preferably contains a polyvalent acid metal salt containing a metal atom and a polyvalent acid. By containing the polyvalent acid metal salt in the silicon polymer composite, the polyvalent acid metal salt acts as a charge injection site, and can achieve higher charge injection characteristics. As a result, a sufficient charge amount can be obtained, and a greater fogging suppression effect can be obtained.
[0064] There is no particular limitation on the polyvalent acid, so long as it is a divalent or higher acid. A salt composed of a divalent or higher acid and a metal atom creates a cross-linked structure between the compound containing the metal atom and the polyvalent acid, and this cross-linked structure promotes the transfer of electrons, improving the efficiency of injection charging.
[0065] Specific examples of polyvalent acids include inorganic acids such as phosphoric acid (trivalent), carbonic acid (divalent), and sulfuric acid (divalent); and organic acids such as dicarboxylic acid (divalent) and tricarboxylic acid (trivalent). Specific examples of organic acids include at least one selected from the group consisting of dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, maleic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, and terephthalic acid; and tricarboxylic acids such as citric acid, aconitic acid, and trimellitic anhydride. Among these, at least one selected from the group consisting of phosphoric acid, carbonic acid, and sulfuric acid is preferred, and phosphoric acid is more preferred.
[0066] Specific examples of polyvalent acid metal salts combining the above metals and the above polyvalent acids include at least one selected from the group consisting of metal phosphates such as titanium phosphate compounds, zirconium phosphate compounds, aluminum phosphate compounds, and copper phosphate compounds; metal sulfates such as titanium sulfate compounds, zirconium sulfate compounds, and aluminum sulfate compounds; metal carbonates such as titanium carbonate compounds, zirconium carbonate compounds, and aluminum carbonate compounds; and metal oxalates such as titanium oxalate compounds. Among these, at least one selected from the group consisting of metal phosphates is preferred because the phosphate ions crosslink the metals, resulting in high strength, and a titanium phosphate compound is even more preferred.
[0067] The method for obtaining the polyvalent acid metal salt is not particularly limited, and any known method can be used. Among them, a method for obtaining the polyvalent acid metal salt by reacting a metal compound as a metal source with a polyvalent acid ion in an aqueous medium is preferred. That is, the polyvalent acid metal salt is preferably a reaction product of a metal compound and a polyvalent acid ion. When a polyvalent acid metal salt is obtained by the above-mentioned method, any known metal compound can be used as the metal source without particular limitation, so long as it is a metal compound that gives a polyvalent acid metal salt by reaction with a polyvalent acid ion.
[0068] Among these, metal chelates are preferred because the reaction is easy to control and they react quantitatively with polyvalent acid ions, and lactate chelates such as titanium lactate and zirconium lactate are more preferred from the viewpoint of solubility in aqueous media.
[0069] Specific examples of the metal source include at least one selected from the group consisting of metal chelates such as titanium lactate, titanium tetraacetylacetonate, titanium lactate ammonium salt, titanium triethanolamine, zirconium lactate, zirconium lactate ammonium salt, aluminum lactate, aluminum trisacetylacetonate, and copper lactate; and metal alkoxides such as titanium tetraisopropoxide, titanium ethoxide, zirconium tetraisopropoxide, and aluminum trisisopropoxide.
[0070] When a polyvalent acid metal salt is obtained by the above method, the polyvalent acid ion may be the ion of the above-mentioned polyvalent acid. When the polyvalent acid metal salt is added to the aqueous medium, the polyvalent acid itself may be added, or a water-soluble polyvalent acid metal salt may be added to the aqueous medium and dissociated in the aqueous medium.
[0071] The toner base particles preferably contain a condensation product of an organosilicon compound. The normalized intensity of silicon ions (m / z=28) derived from the condensation product of the organosilicon compound and represented by the following formula (I) in time-of-flight secondary ion mass spectrometry TOF-SIMS of the toner base particles is: 7.00×10 -4 ~3.00×10 -2 It is preferable that the ratio is 1.00×10 -3 ~1.00×10 -2 It is more preferable that: Normalized silicon ion intensity (m / z=28)={ion intensity of silicon ion (m / z=28)} / {total ion intensity from m / z=0.5 to 1850} (I)
[0072] The normalized intensity in the above range indicates that there is an extremely small amount of silicon ions on the toner base particle surface compared to the prior art. Here, the toner base particle surface is the surface excluding the silicon polymer composite described above. For example, it is the surface of the toner base particle before the silicon polymer composite is applied to the toner base particle. As a means for obtaining a normalized strength in the above range, there can be mentioned means such as using a very small amount of an organosilicon compound during the production of the toner base particles, controlling the hydrolysis of the organosilicon compound, and shortening the condensation time.
[0073] The normalized intensity of silicon ion (m / z=28) is 7.00×10 -4 In the above cases, the charge injection property is sufficiently exhibited, and excellent charging performance is obtained, so that the fogging suppression effect is further increased. The mechanism by which the above-mentioned effects are obtained is believed to be as follows. After the silicon polymer composite is charged in the injection charging process, it is believed that the charge is transferred to the condensation product of the organosilicon compound having a silyl group that is easily negatively charged on the surface of the toner base particle. The affinity between the silicon polymer composite and the condensation product of the organosilicon compound is very high, allowing for rapid charge transfer. The transferred charge is retained on the surface of the toner base particle covered with the silicon polymer composite, which is believed to result in less charge leakage and more stable charging characteristics. Furthermore, the condensation product of the organosilicon compound has an interaction with the binder resin, so that the silicon polymer composite and the binder resin can be firmly bound together, and therefore the electrostatic charge can be maintained more stably and excellently even when used for a long period of time.
[0074] Furthermore, the normalized intensity of silicon ions (m / z=28) is 3.00×10 -2 The charge retention is better in the following cases: The mechanism by which the above-mentioned effects are obtained is considered to be as follows. When a large amount of condensation products of organosilicon compounds are present, a conductive path is formed over the entire surface of the toner base particle. As a result, charges are transferred to the parts of the toner surface that are not covered by the silicon polymer composite, and these parts may act as charge leak sites. As mentioned above, when the normalized intensity of silicon ions (m / z=28) is 3.00×10 -2 In the following cases, the condensation product of the organosilicon compound is present in only a very small amount near the surface of the toner particles. Therefore, the charge transfer to the area not covered with the silicon polymer composite can be suppressed, and the charge retention is further improved. This leads to better transferability.
[0075] In addition, after sputtering the toner base particles with an Ar gas cluster ion beam Ar-GCIB under the following condition (A), the normalized intensity of silicon ions (m / z=28) measured by time-of-flight secondary ion mass spectrometry was 6.99×10 -4 It is preferable that: (A) Conditions Acceleration voltage: 5 kV, current: 6.5 nA, raster size: 600 × 600 μm, irradiation time: 5 sec / cycle, sputtering time: 250 sec
[0076] By performing sputtering under condition (A), it is possible to evaluate silicon ions originating from the condensation product of the organosilicon compound present inside the toner base particles. The amount of condensation products of the organosilicon compound inside the toner particles is small, that is, the normalized intensity of silicon ions (m / z=28) is 6.99×10 -4 When the above range is satisfied, the charge transfer to the whole toner can be suppressed, and therefore the toner covered with the silicon polymer composite can be easily obtained. This makes it easier for the toner base particles to retain charge on their surfaces, which is believed to result in improved charge retention and better transferability. The normalized intensity of silicon ions (m / z=28) after sputtering is more preferably 1.00×10 -5 ~6.99×10 -4 It is.
[0077] Any method may be used to obtain toner particles having a desired silicon ion (m / z=28) normalized intensity. For example, when a condensation product of a silane coupling agent is used as the condensation product of an organosilicon compound, a method of adding a silane coupling agent appropriately in a process of dissolving or dispersing a polymerizable monomer or in a process of polymerizing a polymerizable monomer to obtain toner particles and then carrying out condensation polymerization can be mentioned. Also, a method of adding a silane coupling agent to a dispersion liquid of toner particles and carrying out condensation polymerization can be mentioned. By controlling the timing of adding the polymerizable monomer, the location of silicon ions in the toner can be controlled.
[0078] Since an optimal pH for the condensation polymerization reaction of an organosilicon compound may exist, the reaction can be effectively carried out by condensing the organosilicon compound at an optimal pH for the condensation polymerization reaction. As a method for adding an organosilicon compound such as a silane coupling agent, the organosilicon compound may be added as it is, or may be mixed with an aqueous medium in advance and hydrolyzed before being added.
[0079] Methods for controlling the normalized intensity of silicon ions (m / z=28) near the surface of or inside the toner particles include, for example, methods for controlling the amount of an organosilicon compound added to form a condensation product of the organosilicon compound, the polymerization conversion rate of a polymerizable monomer, the hydrolysis time after addition of the organosilicon compound, or the condensation polymerization time.
[0080] Examples of the condensation products of organosilicon compounds include condensation products of organosilicon compounds such as silane coupling agents, silane-modified resins reacted with silane coupling agents or hydrosilanes, polymers of organosilicon compounds, hybrid resins thereof, condensation products of combinations of these, etc. Among these, condensation products of organosilicon compounds such as silane coupling agents are preferred in that they facilitate control of dispersibility in toner mother particles and the normalized intensity of silicon ions (m / z=28).
[0081] As the silane coupling agent for forming the condensation product of the organosilicon compound, a known organosilicon compound can be used without any particular limitation.Specific examples thereof include the following bifunctional silane compounds having two functional groups and trifunctional silane compounds having three functional groups. Examples of bifunctional silane compounds include dimethyldimethoxysilane and dimethyldiethoxysilane.
[0082] Examples of trifunctional silane compounds include the following. Trifunctional silane compounds having an alkyl group as a substituent, such as methyltrimethoxysilane, methyltriethoxysilane, methyldiethoxymethoxysilane, methylethoxydimethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, etc.; trifunctional silane compounds having an alkenyl group as a substituent, such as vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, etc.; trifunctional silane compounds having an aryl group as a substituent, such as phenyltrimethoxysilane, phenyltriethoxysilane, etc.; γ-methacryloxypropyltrimethoxysilane Silane, trifunctional silane compounds having a methacryloxyalkyl group as a substituent, such as γ-methacryloxypropyltriethoxysilane, γ-methacryloxyoctyltrimethoxysilane, γ-methacryloxypropyldiethoxymethoxysilane, γ-methacryloxypropylethoxydimethoxysilane, and 3-methacryloxypropyltris(trimethylsiloxy)silane; and trifunctional silane compounds having an acryloxyalkyl group as a substituent, such as γ-acryloxypropyltrimethoxysilane, γ-acryloxypropyltriethoxysilane, γ-acryloxyoctyltrimethoxysilane, γ-acryloxypropyldiethoxymethoxysilane, and γ-acryloxypropylethoxydimethoxysilane.
[0083] Materials that can be used in the toner other than the above-mentioned materials will be described in detail below. <Binding resin> The toner base particles contain a binder resin. As the binder resin, known resins can be used without any particular limitation. Specific examples include vinyl resins, polyester resins, polyurethane resins, and polyamide resins. Polymerizable monomers (vinyl monomers) that can be used to manufacture vinyl resins include styrene monomers such as styrene and α-methylstyrene; acrylic acid esters such as methyl acrylate and butyl acrylate; methacrylic acid esters such as methyl methacrylate, 2-hydroxyethyl methacrylate, t-butyl methacrylate, and 2-ethylhexyl methacrylate; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated dicarboxylic acids such as maleic acid; unsaturated dicarboxylic anhydrides such as maleic anhydride; nitrile vinyl monomers such as acrylonitrile; halogen-containing vinyl monomers such as vinyl chloride; and nitro vinyl monomers such as nitrostyrene. In order to reduce the environmental load, biomass-derived styrene and biomass-derived butyl acrylate can be used. The biomass-derived styrene and biomass-derived butyl acrylate may be used alone or in combination.
[0084] Among them, it is preferable that the binder resin contains a vinyl resin or a polyester resin.
[0085] <Coloring agent> The toner base particles may contain a colorant. As the colorant, there is no particular limitation, and conventionally known pigments and dyes of black, yellow, magenta, cyan, and other colors, magnetic materials, and the like can be used. Black colorants include black pigments such as carbon black. Examples of yellow colorants include yellow pigments and yellow dyes such as monoazo compounds, disazo compounds, condensed azo compounds, isoindolinone compounds, benzimidazolone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include CI Pigment Yellow 74, 93, 95, 109, 111, 128, 155, 174, 180, and 185, and CI Solvent Yellow 162.
[0086] Examples of magenta colorants include magenta pigments and magenta dyes such as monoazo compounds, condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, 238, 254, 269, and CI Pigment Violet Red 19.
[0087] Examples of cyan colorants include cyan pigments and cyan dyes such as copper phthalocyanine compounds and derivatives thereof, anthraquinone compounds, and basic dye lake compounds. Specifically, examples include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66. The content of the colorant is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or the polymerizable monomer.
[0088] The toner may also be made magnetic by incorporating a magnetic material, in which case the magnetic material may also function as a colorant. Examples of magnetic materials include iron oxides such as magnetite, hematite, and ferrite; metals such as iron, cobalt, and nickel; and alloys of these metals with metals such as aluminum, cobalt, copper, lead, magnesium, tin, zinc, antimony, beryllium, bismuth, cadmium, calcium, manganese, selenium, titanium, tungsten, and vanadium, and mixtures thereof.
[0089] <Wax> The toner base particles may contain a wax. As the wax, any conventionally known wax may be used without any particular limitation. Specifically, there are esters of monohydric alcohols and monocarboxylic acids, such as behenyl behenate, stearyl stearate, and palmityl palmitate; esters of dihydric carboxylic acids and monoalcohols, such as dibehenyl sebacate; esters of dihydric alcohols and monocarboxylic acids, such as ethylene glycol distearate and hexanediol dibehenate; esters of trihydric alcohols and monocarboxylic acids, such as glycerin tribehenate; esters of tetrahydric alcohols and monocarboxylic acids, such as pentaerythritol tetrastearate and pentaerythritol tetrapalmitate; dipentaerythritol hexastearate and dipentaerythritol tetrastearate; Examples of such waxes include esters of hexahydric alcohols such as tall hexapalmitate and monocarboxylic acids; esters of polyfunctional alcohols such as polyglycerin behenate and monocarboxylic acids; natural ester waxes such as carnauba wax and rice wax; petroleum-based hydrocarbon waxes and their derivatives such as paraffin wax, microcrystalline wax, and petrolatum; hydrocarbon waxes and their derivatives produced by the Fischer-Tropsch process; polyolefin-based hydrocarbon waxes and their derivatives such as polyethylene wax and polypropylene wax; higher aliphatic alcohols; fatty acids such as stearic acid and palmitic acid; and acid amide waxes.
[0090] From the viewpoint of releasability, the content of the wax is preferably from 1.0 to 30.0 parts by mass, and more preferably from 5.0 to 20.0 parts by mass, relative to 100.0 parts by mass of the binder resin or polymerizable monomer.
[0091] <Charge control agent> The toner may contain a charge control agent within the range that does not impair the above-mentioned characteristics or effects. As the charge control agent, any known charge control agent can be used without any particular limitation. Specific examples of the negative charge control agent include metal compounds of aromatic carboxylic acids such as salicylic acid, alkylsalicylic acid, dialkylsalicylic acid, naphthoic acid, and dicarboxylic acids, or polymers or copolymers having metal compounds of the aromatic carboxylic acids; polymers or copolymers having a sulfonic acid group, a sulfonate salt group, or a sulfonate ester group; metal salts or metal complexes of azo dyes or azo pigments; boron compounds, silicon compounds, and calixarenes.
[0092] On the other hand, examples of the positive charge control agent include the following: quaternary ammonium salts, polymeric compounds having quaternary ammonium salts in the side chains; guanidine compounds; nigrosine compounds; imidazole compounds. In addition, polymers or copolymers having sulfonate groups or sulfonate ester groups are also usable. As the polymer, a homopolymer of a sulfonic acid group-containing vinyl monomer such as styrene sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 2-methacrylamido-2-methylpropanesulfonic acid, vinyl sulfonic acid, or methacrylsulfonic acid, or a copolymer of a vinyl monomer listed in the section on binder resin and the above-mentioned sulfonic acid group-containing vinyl monomer, can be used. The content of the charge control agent is preferably 0.01 parts by mass or more and 5.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or polymerizable monomer.
[0093] <External additives> When the toner particles have a silicon polymer composite on the surface, they exhibit excellent properties such as flowability even in the absence of external additives. However, for the purpose of further improvement, external additives may be included within the range that does not impair the above properties or effects. As the external additive, there is no particular limitation and any external additive known in the art can be used.
[0094] Specific examples of the silica fine particles include: raw silica fine particles such as wet-process silica and dry-process silica, and silica fine particles obtained by subjecting such raw silica fine particles to a surface treatment with a treating agent such as a silane coupling agent, a titanium coupling agent, or silicone oil; and resin fine particles such as vinylidene fluoride fine particles and polytetrafluoroethylene fine particles. The content of the external additive is preferably 0.1 parts by mass or more and 5.0 parts by mass or less with respect to 100.0 parts by mass of the toner particles.
[0095] Next, a method for obtaining the toner will be described in detail below. <Method of manufacturing toner base particles> The method for producing the toner base particles (the toner particles before the silicon polymer composite is attached are also referred to as "toner base particles") is not particularly limited, and the suspension polymerization method, the solution suspension method, the emulsion aggregation method, the pulverization method, etc. can be used.
[0096] As an example, a method for obtaining toner base particles by suspension polymerization will be described below. First, a polymerizable monomer capable of forming a binder resin and, if necessary, various additives are mixed, and the materials are dissolved or dispersed using a disperser to prepare a polymerizable monomer composition. The various additives include colorants, waxes, charge control agents, polymerization initiators, chain transfer agents, and the like. Examples of the dispersing machine include a homogenizer, a ball mill, a colloid mill, and an ultrasonic dispersing machine.
[0097] Next, the polymerizable monomer composition is added to an aqueous medium containing poorly water-soluble inorganic fine particles, and droplets of the polymerizable monomer composition are prepared using a high-speed disperser such as a high-speed stirrer or an ultrasonic disperser (granulation process). Thereafter, the polymerizable monomer in the droplets is polymerized to obtain toner base particles (polymerization step). In the polymerization step, it is preferable to polymerize the polymerizable monomer, and then add an organosilicon compound to form a condensation product of the organosilicon compound, and perform condensation polymerization. This makes it easier to achieve the above-mentioned silicon ion (m / z=28) normalized intensity.
[0098] The polymerization initiator may be mixed when the polymerizable monomer composition is prepared, or may be mixed into the polymerizable monomer composition immediately before forming droplets in the aqueous medium. Alternatively, the compound may be added in a state dissolved in the polymerizable monomer or in another solvent, as required, during or after the granulation of the droplets, that is, immediately before the start of the polymerization reaction. After obtaining a binder resin by polymerizing the polymerizable monomer, a solvent removal treatment may be carried out as necessary to obtain a dispersion liquid of toner base particles.
[0099] When the binder resin is obtained by the emulsion aggregation method or the suspension polymerization method, the polymerizable monomer may be any known monomer without any particular limitation. Specifically, the vinyl monomers listed in the section on the binder resin may be used.
[0100] As the polymerization initiator, any known polymerization initiator can be used without any particular limitation. Specific examples thereof include the following.
[0101] Hydrogen peroxide, acetyl peroxide, cumyl peroxide, tert-butyl peroxide, propionyl peroxide, benzoyl peroxide, chlorobenzoyl peroxide, dichlorobenzoyl peroxide, bromomethylbenzoyl peroxide, lauroyl peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, diisopropyl peroxycarbonate, tetralin hydroperoxide, 1-phenyl-2-methylpropyl-1-hydroperoxide, pertriphenylacetic acid-tert-hydroperoxide, tert-butyl performate, tert-butyl peracetate, tert-butyl perbenzoate, tert-butyl perphenylacetate, tert-butyl permethoxyacetate, per-N-(3-tolyl)palmitate-tert-butylbenzoyl peroxide, t-butyl peroxybenzoyl peroxide, Examples of the polymerization initiator include peroxide-based polymerization initiators such as butyl peroxy 2-ethylhexanoate, t-butyl peroxy pivalate, t-butyl peroxy isobutyrate, t-butyl peroxy neodecanoate, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide; and azo- or diazo-based polymerization initiators such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile.
[0102] Method for depositing silicon polymer composites Examples of methods for adhering the silicon polymer composite to the toner base particles include a method in which a metal compound serving as a metal source is reacted with a silicon compound (preferably an organosilicon compound) in an aqueous medium in which the toner base particles are dispersed to obtain the silicon polymer composite, and a method in which the silicon polymer composite is adhered to the toner particles by mechanical external force in a dry or wet manner.
[0103] (1) A method of obtaining a silicon polymer composite by reacting a metal compound serving as a metal source with a silicon compound in an aqueous medium in which toner base particles are dispersed. For example, a compound containing a metal element and a silicon compound are added to a dispersion liquid of toner base particles and mixed to cause a reaction between the compound containing a metal element and the silicon compound, and the reactant is precipitated. At the same time, the dispersion liquid is stirred to cause the reactant to adhere to the toner base particles.
[0104] (2) A method in which a silicon polymer composite is attached to the surface of a toner base particle by mechanical external force in a dry or wet manner. For example, a high-speed agitator that applies shear force to powder or aqueous medium, such as an FM Mixer, Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.), Super Mixer, Nobilta (manufactured by Hosokawa Micron Corporation), or TK Homo Mixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), is used to apply a force that disintegrates the silicon polymer composite while causing the silicon polymer composite to adhere to the toner base particles.
[0105] Among them, (1) a method of obtaining a silicon polymer composite by reacting a metal compound serving as a metal source with an organosilicon compound in an aqueous medium in which toner base particles are dispersed is preferred. By using the above method, it is possible to uniformly disperse the silicon polymer composite on the toner particle surface. The uniform presence of charge injection sites on the toner particle surface allows charge to be uniformly and efficiently injected into the toner, improving the charge rise property and further suppressing fogging.
[0106] Furthermore, according to the above method, the silicon polymer composite formed in the aqueous medium adheres to the toner base particles before the growth is completed, so that the silicon polymer composite is more strongly fixed to the toner base particles than when a pre-prepared silicon polymer composite is adhered by mechanical external force, and therefore, even when used for a long period of time, the silicon polymer composite does not separate from the base, and a toner with excellent durability can be obtained that can exert the effect of the present invention, which is improved fogging suppression, over a long period of use.
[0107] The method (1) is illustrated below. When the silicon polymer composite is adhered to the toner base particles by a method in which a metal compound serving as a metal source is reacted with a silicon compound in an aqueous medium in which the toner base particles are dispersed to obtain a silicon polymer composite, the method preferably includes the following steps: That is, the method for producing the toner is as follows: A step (step 1) of dispersing toner base particles in an aqueous medium to obtain a toner base particle dispersion; and A step (step 2) of mixing a metal compound and a silicon compound (or a hydrolyzate thereof) into the toner base particle dispersion and reacting the metal compound and the silicon compound in the toner base particle dispersion to adhere a silicon polymer composite onto the toner base particles. It is preferred that the compound contains
[0108] In the above step 1, the method for obtaining the toner base particle dispersion may include a method of using the dispersion of toner base particles produced in an aqueous medium as is, and a method of putting dried toner base particles into an aqueous medium and dispersing them mechanically, etc. When dispersing dried toner base particles in an aqueous medium, a dispersion aid may be used.
[0109] As the dispersion aid, known dispersion stabilizers and surfactants can be used. Specifically, the dispersion stabilizer includes inorganic dispersion stabilizers such as tricalcium phosphate, hydroxyapatite, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silica, and alumina, and organic dispersion stabilizers such as polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch. In addition, the surfactant includes anionic surfactants such as alkyl sulfate ester salts, alkylbenzene sulfonates, and fatty acid salts, nonionic surfactants such as polyoxyethylene alkyl ethers and polyoxypropylene alkyl ethers, and cationic surfactants such as alkylamine salts and quaternary ammonium salts. Among them, it is preferable to include an inorganic dispersion stabilizer, and it is more preferable to include a dispersion stabilizer containing a phosphate such as tricalcium phosphate, hydroxyapatite, magnesium phosphate, zinc phosphate, or aluminum phosphate.
[0110] In the above step 2, the silicon compound may be added to the toner base particle dispersion liquid as it is, or may be added to the toner base particle dispersion liquid after hydrolysis. Among them, it is preferable to add the silicon compound after hydrolysis, since the reaction between the metal compound and the silicon compound is easily controlled and the amount of the silicon compound remaining in the toner base particle dispersion liquid can be reduced. The hydrolysis is preferably carried out in an aqueous medium whose pH is adjusted using known acid and base.It is known that the hydrolysis of organosilicon compounds is pH-dependent, and the pH of the hydrolysis is preferably appropriately changed according to the type of organosilicon compound.For example, when methyltriethoxysilane is used as organosilicon compound, the pH of the aqueous medium is preferably 2.0 or more and 6.0 or less.
[0111] The acids used to adjust the pH are as follows: hydrochloric acid, hydrobromic acid, and hydrogen iodide. Examples of the acid include inorganic acids such as acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, hypobromous acid, bromous acid, bromic acid, perbromic acid, hypoiodous acid, iodous acid, iodic acid, periodic acid, sulfuric acid, nitric acid, phosphoric acid, and boric acid; and organic acids such as acetic acid, citric acid, formic acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid.
[0112] Specific examples of bases for adjusting the pH include the following: alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, lithium hydroxide, etc., and aqueous solutions of these; alkali metal carbonates such as potassium carbonate, sodium carbonate, lithium carbonate, etc., and aqueous solutions of these; alkali metal sulfates such as potassium sulfate, sodium sulfate, lithium sulfate, etc., and aqueous solutions of these; alkali metal phosphates such as potassium phosphate, sodium phosphate, lithium phosphate, etc., and aqueous solutions of these; alkaline earth metal hydroxides such as calcium hydroxide, magnesium hydroxide, etc., and aqueous solutions of these; and amines such as ammonia and triethylamine.
[0113] The reaction between the metal compound and the silicon compound in the above step 2 is preferably controlled by adjusting the pH of the toner base particle dispersion liquid. The reaction between the metal compound and the silicon compound is known to be pH-dependent, and it is preferable to appropriately change the pH when the reaction between the metal compound and the silicon compound is carried out depending on the type of the metal compound and the silicon compound. For example, when titanium lactate is used as the metal compound and methyltriethoxysilane is used as the silicon compound, the pH of the aqueous medium is preferably 6.0 to 12.0. The acids and bases for adjusting the pH can be the acids and bases exemplified in the section on hydrolysis above.
[0114] In step 2, the pH when the metal compound and the silicon compound (or their hydrolysate) are mixed into the toner base particle dispersion is preferably a pH at which condensation of the silicon compound does not easily proceed, for example, preferably 2.0 to 6.0, more preferably 4.0 to 6.0. It is preferable to mix the metal compound and the silicon compound (or their hydrolysate) into the toner base particle dispersion and control the pH. The pH in step 2 is preferably 8.5 to 10.5, more preferably 9.0 to 10.0. The pH adjustment time when the pH control is performed is preferably 1 to 90 minutes, more preferably 1 to 40 minutes. By changing the pH during the adjustment time, the hydrolysis of the metal compounds can be promoted while suppressing the condensation reaction between the metal compounds.
[0115] The condensation reaction in step 2 is preferably carried out at about 10 to 100° C., more preferably at 30 to 70° C. The ME, SiE, MX, Mmax, Mave, etc. can be arbitrarily controlled by adjusting the amount of each material added, the timing of addition, the temperature, the pH, and other conditions.
[0116] (ME / SiE) / MX can be increased by increasing the pH in step 2 or by increasing the amount of silane coupling agent above a certain level. (ME / SiE) / MX can be decreased by decreasing the pH or temperature in step 2 or by reducing the amount of metal compound added. MX can be increased by increasing the amount of the metal compound added, and can be decreased by decreasing the amount of the metal compound added. In addition, Mmax / Mave can be increased by increasing the amount of silane coupling agent added or by decreasing the reaction temperature or pH. Mmax / Mave can be decreased by increasing the amount of metal compound added or by increasing the reaction temperature or pH.
[0117] In addition, the silicon polymer composite preferably contains a polyvalent acid metal salt. In step 2, if a polyvalent acid is present in the toner base particle dispersion, the reaction between the metal compound and the polyvalent acid also proceeds at the same time. Polyvalent acid metal salt is generated. As a result, the polyvalent acid metal salt can be contained in the silicon polymer composite. The condensation reaction between silicon compounds, the reaction between a metal compound and a silicon compound, and the reaction between a metal compound and a polyvalent acid occur competitively, so they can be controlled arbitrarily by adjusting the amount of each material added, the timing of addition, temperature, pH, and other conditions.
[0118] For example, a dispersion aid containing polyvalent acid ions such as phosphate ions can be selected for use in step 1. The toner base particle dispersion obtained in step 1 can contain polyvalent acid ions. This allows the polyvalent acid ions to react with the metal compound when the silicon polymer composite is reacted with the silicon compound in step 2.
[0119] In order to achieve the above-mentioned effects more significantly, it is preferable to control the shape of the silicon polymer composite, the amount of metal atoms, the exposed ratio of metal atoms, the dispersibility of metal atoms, and the chemical bond between the metal atoms and the silicon polymer. These can be controlled as desired by adjusting the production conditions such as the amount and timing of addition of each material in the above-mentioned steps 1 and 2, temperature, and pH.
[0120] As the metal compound, silicon compound, and polyvalent acid used in the above method, the above-mentioned metal compound, silicon compound, and polyvalent acid can be used, respectively.
[0121] Next, methods for measuring the various physical properties of the photoreceptor and toner according to the present invention will be described in detail below. In the explanation of each measuring method, the toner, toner particles, or toner base particles will also be referred to as "toner, etc."
[0122] <Method of observing the toner surface> The toner surface is observed as follows. A scanning electron microscope (SEM, device name: JSM-7800F, manufactured by JEOL Ltd.) is used to observe the surface of the toner, etc., at a magnification of 50,000 times. Then, elements on the surface of the toner, etc. are mapped using EDX (energy dispersive X-ray spectroscopy). The presence of silicon polymer composites and polyvalent acid metal salts on the surface of the toner is confirmed from the positions of the elements confirmed in the obtained SEM element mapping image and the positions of the elements confirmed in the EDX mapping image of the toner obtained by the <Method of observing the cross section of the toner> described below.
[0123] Specifically, by comparing the mapping image of silicon with the mapping image of a metal element, it can be confirmed that silicon and a metal element exist in the same particle, and therefore the metal atom and silicon atom exist as a silicon polymer composite. Furthermore, by comparing the mapping image of the metal element with the mapping image of an element contained in the polyvalent acid, for example, phosphorus when phosphoric acid is used as the polyvalent acid, and finding that the two match, it can be confirmed that the sample contains a polyvalent acid metal salt.
[0124] <Method of observing the cross section of toner (MX measurement)> First, the toner is spread on a cover glass (Matsunami Glass Co., Ltd., square cover glass No. 1) so that it becomes a single layer, and then an Os film (5 nm) and a naphthalene film (20 nm) are applied to the toner as a protective film using an osmium plasma coater (Filgen Co., Ltd., OPC80T). Next, a PTFE tube (inner diameter 1.5 mm × outer diameter 3 mm × 3 mm) is filled with photocurable resin D800 (JEOL Co., Ltd.), and the cover glass is gently placed on top of the tube so that the toner is in contact with the photocurable resin D800. In this state, the resin is irradiated with light to harden it, and then the cover glass and tube are removed to form a cylindrical resin with toner embedded in its outermost surface. Using an ultrasonic ultramicrotome (Leica, UC7), the resin is cut at a cutting speed of 0.6 mm / s from the outermost surface of the cylindrical resin to the length of the toner radius (4.0 μm when the weight average particle diameter (D4) is 8.0 μm). The toner cross section was then cut to a thickness of 100 nm to create a thin sample of the toner cross section. By cutting in this way, the cross section of the center of the toner can be obtained. This thin sample was observed in STEM mode of a scanning transmission electron microscope (JEOL, JEM2800) connected to an EDS analyzer (energy dispersive X-ray analyzer) at a magnification of 400,000 times, in a field of view where the outermost surface of the toner could be confirmed.
[0125] The constituent elements of the cross section of the observed toner were collected by an EDS analyzer, and an EDS mapping image was created. The collection and analysis of the spectrum was performed using an NSS (ThermoFischer Scientific). The collection conditions were an accelerating voltage of 200 The probe size was appropriately selected to be 1.0 nm or 1.5 nm so that the kV and dead time were 15 to 30, the mapping resolution was 256 × 256, and the number of frames was 500. EDS mapping images were obtained for 30 cross sections of the toner.
[0126] In the EDS mapping image thus obtained, signals originating from the constituent elements of the silicon polymer composite and polyvalent acid metal salt particles are confirmed on the contour of the cross section of the toner. This allows the presence or absence of convex portions on the toner surface, and the presence of silicon polymer composites and polyvalent acid metal salt particles to be confirmed. Furthermore, the composition of the convex portions, i.e., whether the convex portions are formed of silicon polymer composites, is confirmed.
[0127] Furthermore, by analyzing the EDS mapping image obtained as described above, the ratio of the number of metal atoms to the sum of the numbers of silicon atoms and the metal atoms in the silicon polymer composite can be calculated.
[0128] First, press the "Extract from line" button in NSS and select the analysis range freehand. Specifically, trace the interface between the toner base particle and the silicon polymer composite present on the surface of the toner base particle to draw a baseline, and then draw a parallel line 200 nm away from the baseline toward the outer edge of the toner. The range between the baseline and the parallel line is selected as the analysis range, and this range will be the area outside the outline of the toner base particle. Once the toner analysis range has been selected, the ratio (atomic %) of silicon atoms and the metal atoms in the selected range is automatically calculated by pressing the "Spectrum Quantitation" button. At this time, silicon and the metal element are selected as the elements to be analyzed. Based on the values of the silicon atom ratio (atomic %) and the metal atom ratio (atomic %) displayed in the quantification results, the ratio MX of the number of the metal atoms in the sum of the number of silicon atoms and the number of the metal atoms in the silicon polymer composite can be calculated. That is, MX=(number of the metal atoms) / (sum of the numbers of silicon atoms and the metal atoms). The arithmetic average value of 30 cross sections of the toner is used. Figure 1 is an example of a STEM image of the toner used in the examples. In Figure 1, the group of white convex shapes is the silicon polymer composite, and the lower left is the toner base particle portion excluding the convex shapes. In addition, when the silicon polymer composite is present in a semi-spherical shape at the interface between the silicon polymer composite and the binder resin as shown in Figure 1, it is determined that "the silicon polymer composite is adhered to the surface of the toner base particle in a convex shape."
[0129] <Method for evaluating the dispersion of specific metal atoms (measurement of Mmax and Mave)> Using the EDS mapping image obtained by the above <Method for Observing a Cross Section of a Toner>, the fine dispersion of a specific metal atom in a silicon polymer composite can be quantified and evaluated. First, a baseline is determined by connecting the endpoints of the interface formed by the image of the toner base particle and the image of the silicon polymer composite with a straight line, as observed in the EDS mapping image, and then a perpendicular line L1 with the maximum length is determined among the perpendicular lines connecting the baseline and the outer surface of the image of the silicon polymer composite. Next, when the width of the image of the silicon polymer composite, which is the length of the baseline, is defined as W, a line segment L2 is defined on the baseline by connecting two points on the baseline that are 0.1W inward from each end of the baseline. Then, the line segment L2 is moved parallel to the base line in the direction in which the perpendicular line L1 extends to the position of the midpoint of the perpendicular line L1, and the area where the moved line segment overlaps with the image of the silicon polymer composite is defined as "area X." Furthermore, information on the detection intensity (net count) of atoms in the region X is obtained. Specifically, the "Extract Line" button is pressed, the above line segment is drawn, and the "Spectrum Quantitation" button is pressed, whereby the intensity of the specific metal atom on the line segment is automatically calculated. At this time, the specific metal element is selected as the element to be analyzed. The maximum value of the net count of a specific metal element obtained from this line is designated as Mmax, and the average value is designated as Mave.
[0130] <Method for measuring the ratio of silicon atoms and specific metal atoms (ME / SiE)> The ratio of the number of silicon atoms and the number of specific metal atoms to the total number of carbon atoms, oxygen atoms, silicon atoms, phosphorus atoms and specific metal atoms on the surface of the toner is calculated as follows. The conditions when titanium atoms are used as the specific metal atoms are exemplified below. When other metal atoms are used, the quantitative value is calculated using a peak corresponding to the peak position of any specific metal atom. The following apparatus is used under the following conditions to perform elemental analysis of the toner surface. Measurement device: Quantum2000 (product name, manufactured by ULVAC-PHI, Inc.) X-ray source: Monochrome Al Kα ·Xray Setting:100μmφ(25W(15KV)) Photoelectron take-off angle: 45 degrees Neutralization Condition: Use Neutralization Gun and Ion Gun together ·Analysis area: 300×200μm Pass Energy: 58.70eV Step size: 1.25eV Analysis software: Maltipak (PHI) Here, the atomic numbers (atomic %) of silicon atoms and titanium metal atoms are calculated using the peaks of C 1c (BE280-295 eV), O 1s (BE525-540 eV), Si 2p (BE95-113 eV), P 2p (BE129-138 eV), and Ti 2p (BE456-470 eV). The sum of the atomic numbers of carbon atoms, oxygen atoms, silicon atoms, phosphorus atoms, and titanium atoms is calculated. The ratio of the number of silicon atoms to the sum of these atomic numbers is SiE, and the ratio of the number of titanium atoms is ME. That is, SiE=(the number of silicon atoms) / (the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, phosphorus atoms, and titanium atoms). Furthermore, ME=(the number of titanium atoms) / (the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, phosphorus atoms, and titanium atoms). ME / SiE is calculated from the obtained ME and SiE.
[0131] <Method of confirming that a silicon polymer composite contains a silicon polymer> The silicon polymer composite contained in the toner or the like contains a silicon polymer. 13 C-NMR, 29 Confirm by Si-NMR. The equipment and measurement conditions used are shown below. "Measurement conditions" Equipment: BRUKER AVANCE III 500 Probe: 4mm MAS BB / 1H Measurement temperature: room temperature Sample rotation speed: 6kHz Sample: 150 mg of a measurement sample (a tetrahydrofuran (THF) insoluble matter such as a toner for NMR measurement) is placed in a sample tube with a diameter of 4 mm. The presence or absence of a silicon polymer is confirmed by this method. If a signal derived from the silicon polymer is confirmed, it is determined that the silicon polymer composite contains a silicon polymer.
[0132] " 13C-NMR (solid state) measurement conditions Measurement nuclear frequency: 125.77MHz Reference substance: Glycine (external standard: 176.03ppm) Observation width: 37.88kHz Measurement method: CP / MAS Contact time: 1.75ms Repeat time: 4s Accumulation count: 2048 times LB value: 50Hz
[0133] " 29 "Si-NMR (solid state) measurement method" "Measurement conditions" Equipment: BRUKER AVANCE III 500 Probe: 4mm MAS BB / 1H Measurement temperature: room temperature Sample rotation speed: 6kHz Sample: 150 mg of a measurement sample (THF insoluble portion of toner particles for NMR measurement) is placed in a sample tube with a diameter of 4 mm. Measurement nuclear frequency: 99.36MHz Reference material: DSS (external standard: 1.534ppm) Observation width: 29.76kHz Measurement method: DD / MAS, CP / MAS 29Si 90° Pulse width: 4.00μs@-1dB Contact time: 1.75ms~10ms Repeat time: 30s (DD / MASS), 10s (CP / MAS) Accumulation count: 2048 times LB value: 50Hz
[0134] <Method for measuring electrical conductivity of silicon polymer composite (powder)> The electrical properties of the silicon polymer composites are evaluated by measuring the powder bulk capacitance and conductivity by impedance measurements using the double ring technique with parallel plate electrodes. The equipment used is a powder measurement jig consisting of a four-terminal sample holder SH2-Z (manufactured by Toyo Corporation) and a torque wrench adapter SH-TRQ-AD (optional), and a material testing system ModuLab XM MTS (manufactured by Solartron Corporation).In addition, a noise cut transformer NCT-I3 1.4kVA (manufactured by Denken Seiki Kenkyusho Co., Ltd.) to suppress commercial power supply noise and a shield box to suppress electromagnetic noise are used.
[0135] The powder measurement jig is made up of a four-terminal sample holder and an optional torque wrench adapter SH-TRQ-AD. The parallel plate electrodes are the upper electrode (25 mm diameter solid electrode) SH-H25AU and the lower electrode for liquids / powder (center electrode 10 mm diameter; guard electrode 26 mm diameter) SH-2610AU, and is configured to measure resistances of 0.1 Ω to 1 TΩ for electrical signals of up to 500 Vp-p and DC to 1 MHz. In order to adjust the pressure of the powder sample, a torque wrench adapter SH-TRQ-AD (manufactured by Toyo Corporation) is attached to the micrometer used to measure the film thickness between the upper and lower electrodes provided on the four-terminal sample holder. The torque driver used for pressure control is the torque driver RT Using D15CN and a 6.35 mm square bit, the tightening torque for powder measurement can be controlled to 6.5 cN·m.
[0136] The electrical AC characteristics are measured by impedance measurement using the material testing system ModuLab XM MTS (manufactured by Solartron). ModuLab XM MTS is composed of a control module XM MAT 1MHz, a femto current module XM MFA, and a frequency response analysis module XM MRA 1MHz, and the control software is Solartron's XM-studio MTS Ver.3.4.
[0137] For powder materials such as silicon polymer composites, set the AC level within the range of 7 mVrms to 70 mVrms so that it is within the measurable current range of the measuring instrument. Also, set it to Normal Mode, which only performs measurement, with DC bias of 0 V, sweep frequency of 1 MHz to 100 Hz (12 points / decade), and measurement integration time of 1 second.
[0138] Under the above measurement conditions, the impedance characteristics, which are electrical AC characteristics, are measured. By performing measurements under the above conditions, the impedance characteristics of the powder sample at the film thickness d according to the applied torque and the measurement electrode S having a diameter of 10 mm, which is the powder measurement tool used, can be obtained. From the impedance characteristics of the powder sample thus obtained, the capacitance C and conductance (conductivity) G are obtained. From the obtained capacitance C, conductance (conductivity) G, and the geometric shape of the powder measurement jig (parallel plate electrode size S and sample film thickness), the electrical conductivity, which is an electrical property, is calculated.
[0139] When using the SH2-Z 4-terminal sample holder for the first time, because there are individual differences in the SH2-Z 4-terminal sample holders used in powder measurement fixtures, it is necessary to carry out the following two verifications to find the optimal measurement conditions. The first verification is the film thickness dependency characteristic of the four-terminal sample holder. The dependency on air thickness (distance between the upper and lower electrodes) is measured, the error between the theoretical value of capacitance and the measured value is confirmed, and the optimal range or film thickness that minimizes the measurement error is identified. The second verification was the measurement of mechanical error. When measuring powder samples, a torque-controlled load is applied to keep the volume density constant. In contrast, no load is applied when measuring air. At this time, film thickness errors occur due to the influence of dimensions such as mechanical processing accuracy. Therefore, we checked the offset value of the tightening torque control value (6.5 cN m for this jig) under load and no load conditions to understand the appropriate film thickness range for the powder measurement jig when pressurized in order to obtain highly reliable data.
[0140] Specific sample preparation and measurement procedures are as follows. (1) A powder sample is placed on the central electrode part of the lower electrode and formed into a trapezoidal shape with a height of 5 mm. (2) The lower electrode carrying the powder sample is attached to the four-terminal sample holder SH2-Z, and the upper electrode is lowered. (3) At this time, the upper electrode is lowered to the top end of the powder sample while keeping it constant so as not to rotate inadvertently. (4) While rotating the upper electrode left and right, the powder sample is smoothed until it becomes smooth. (5) Using a micrometer, adjust the film thickness to a desired value while keeping the rotation direction of the upper electrode constant. (6) Apply pressure using a torque driver with the tightening torque controlled at 6.5 cN m. (7) Using a micrometer, measure the film thickness of the powder sample. (8) Impedance measurement is performed under the above conditions. (9) After the measurement is completed, raise the upper electrode and remove the lower electrode. At this time, remove the lower electrode while being careful not to let the powder sample get into the contact terminal for the lower electrode of the four-terminal sample holder, and protect it with masking tape. (10) Clean the upper and lower electrodes. (11) Remove the masking tape and attach the lower electrode.
[0141] The measurements are carried out at 25°C. The specific data processing procedure is as follows. (12) From the impedance characteristic measured in step (8), a complex admittance Ym=Gm+jωCm is obtained. (Ym is the measured admittance, Gm is the measured conductance, and Cm is the measured capacitance. In addition, ω is the angular frequency, and j is the imaginary number of a complex number.) (13) The electrical conductivity κ can be calculated from the conductance Gm and the geometric shape of the powder measurement jig (measurement electrode area S, measurement film thickness d). κ=Gm×d / S The following describes a method for quantifying electrical conductivity, which is an electrical property.
[0142] (Method of quantifying electrical conductivity) The powder sample, which has both capacitance and conductivity, can be recognized as an RC parallel circuit model, and the conductivity κ in the low frequency range shows a constant value. In this disclosure, the conductivity was measured at a frequency of 10 kHz.
[0143] (Preparation of Silicon Polymer Composite (Powder)) The silicon polymer composite can be recovered from the toner particles by the following procedure, and used as a sample for measuring the dielectric constant. The method for recovering silicon polymer composite from toner particles is explained below. 10.0g of toner particles are weighed and mixed with 100mL of N,N-dimethylformamide (DMF) for 60 minutes by stirring. If necessary, the mixture may be heated up to 80℃ during stirring. After 60 minutes of stirring, the mixture is returned to room temperature and transferred to a glass tube (50mL) for a swing rotor, and centrifuged at 3500rpm for 30 minutes in a centrifuge. After centrifugation, DMF insoluble matter containing silicon polymer composite is present in the lower layer of the glass tube. This insoluble matter is recovered. This operation is repeated three times. The recovered insoluble matter is then dispersed in 100mL of RO water, and centrifuged again in a centrifuge at 3500rpm for 30 minutes. The insoluble matter in the lower layer of the glass tube is recovered and dried to obtain the silicon polymer composite.
[0144] In the examples described below, a silicon polymer composite dispersion was prepared in the absence of toner base particles, and the electrical conductivity of the silicon polymer composite obtained by dehydration was measured. The method for dehydrating the silicon polymer composite dispersion is as follows. First, the solid content is removed from the silicon polymer composite dispersion by centrifugation. Then, the silicon polymer composite dispersion is dispersed again in ion-exchanged water, and the solid content is removed by centrifugation. This process is repeated three times to remove ions such as sodium. The silicon polymer composite is dispersed again in ion-exchanged water and dried by spray drying to obtain a silicon polymer composite.
[0145] <Method of measuring weight average particle size (D4) and number average particle size (D1)> The weight average particle diameter (D4) and number average particle diameter (D1) of the toner or the like are calculated as follows. The measuring device used is a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube. The measurement conditions and data analysis were performed using the dedicated software "Beckman Coulter The system used was "Multisizer 3 Version 3.51" (Beckman Coulter, Inc.). The measurement was performed with an effective measurement channel count of 25,000 channels. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of 1.0%, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.). Before performing measurements and analysis, the dedicated software is set up as follows. In the "Change standard measurement method (SOMME)" screen of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard particle 10.0 μm" (Beckman Coulter, Inc.). Press the "Threshold / Noise level measurement button" to automatically set the threshold and noise level. In addition, set the current to 1,600 μA, the gain to 2, the electrolyte to ISOTON II, and check "Flush aperture tube after measurement." In the "Pulse to particle size conversion setting" screen of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm. The specific measurement method is as follows.
[0146] (1) Pour 200.0 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture tube flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Place 30.0 mL of the electrolyte solution in a 100 mL flat-bottom glass beaker. Add 0.3 mL of a solution of "Contaminon N" (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion-exchanged water as a dispersant. (3) Prepare an ultrasonic disperser "Ultrasonic Dispersion System Tetra150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. Place 3.3 L of ion-exchanged water in the ultrasonic disperser's water tank and add 2.0 mL of Contaminon N to this tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is being irradiated with ultrasonic waves, 10 mg of toner or the like is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted so that it is between 10°C and 40°C. (6) Using a pipette, drip the electrolytic solution (5) in which the toner or the like has been dispersed into the round-bottom beaker (1) placed in the sample stand to adjust the measurement concentration to 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device to calculate the weight average particle size (D4) and number average particle size (D1). When the dedicated software is set to Graph / Volume %, the "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the weight average particle size (D4). When the dedicated software is set to Graph / Number %, the "Average diameter" on the "Analysis / Number Statistics (Arithmetic Mean)" screen is the number average particle size (D1).
[0147] <Method for measuring normalized intensity of silicon ions present on the surface of toner base particles> The normalized intensity of silicon ions (m / z=28) on the surface of the toner base particles is confirmed by a time-of-flight secondary ion mass spectrometer (TOF-SIMS). The equipment and measurement conditions used are shown below. The measurement was performed by washing the toner base particle dispersion with hydrochloric acid, and then washing with ion-exchanged water. The toner base particles obtained by filtration are subjected to the above-mentioned procedure. Measurement device: nanoTOF II (product name, manufactured by ULVAC-PHI, Inc.) Primary ion species: Bi 3++ Acceleration voltage: 30kV Primary ion current: 0.05pA Repetition rate: 8.2kHz Raster mode: Unbunch Raster size: 100μm×100μm Measurement mode: Positive Neutralization gun: Used Measurement time: 600 seconds Sample preparation: Toner base particles are fixed on an indium sheet Sample pretreatment: None Using ULVAC-PHI's standard software (TOF-DR), evaluation is performed based on the mass numbers of Si ions and fragment ions originating from the resin or silane compound. The ion intensity derived from silicon with mass number 28 (m / z=28) is divided by the total ion intensity in the mass numbers 0.5 to 1850 to derive the silicon ion normalized intensity (m / z=28).
[0148] <Method for measuring normalized intensity of silicon ions present inside toner particles> Normally, TOF-SIMS is a surface analysis method, and the data in the depth direction is about 1 nm. Therefore, the strength inside the toner base particle is measured after sputtering the toner base particle with an argon gas cluster ion beam (Ar-GCIB) and scraping the surface. After sputtering the toner base particles under the conditions (A) below, the normalized silicon ion intensity (m / z 28) measured under the same conditions as in the above "Method for measuring normalized silicon ion intensity present on the surface of a toner base particle" is taken as the value of the normalized silicon ion intensity present inside the toner base particle. The sputtering conditions were as follows: (A) Conditions Acceleration voltage: 5 kV Current: 6.5 nA Raster size: 600×600 μm Irradiation time: 5sec / cycle Sputtering time: 250 sec In addition, when we confirmed the cutting depth by sputtering a PMMA film under the same conditions in advance, we confirmed that 80 nm was removed in 250 s.
[0149] <Removal of external additives from toner> If necessary, the external additives may be removed from the toner by the following procedure, and the toner may be used for each analysis. Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Place 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% by weight aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) in a centrifuge tube to prepare a dispersion. Add 1 g of toner to this dispersion and loosen the toner clumps with a spatula or the like. Place the centrifuge tube on a shaker (KM Shaker manufactured by Iwaki Sangyo Co., Ltd.) and shake it for 30 minutes under the condition of 350 reciprocations per minute. After shaking, transfer the solution to a glass tube (50 mL) for a swinging rotor and centrifuge it in a centrifuge (H-9R; manufactured by Kokusan Co., Ltd.) under the condition of 58.33S -1 for 30 minutes. In the glass tube after centrifugation, toner particles exist in the uppermost layer and external additives exist in the aqueous solution layer on the lower layer. The uppermost layer of toner particles is collected, filtered, washed with running water using 2 L of ion-exchanged water warmed to 40°C, and the washed toner particles are taken out.
[0150] <Separation method of THF-insoluble components such as toner for IR (infrared spectroscopy) analysis> The tetrahydrofuran (THF)-insoluble components such as toner were separated as follows. Weigh 10.0 g of toner or the like, put it in a cylindrical filter paper (No. 86R manufactured by Toyo Roshi Kaisha, Ltd.), and place it in a Soxhlet extractor. Extract it for 20 hours using 200 mL of THF as a solvent, and the residue in the cylindrical filter paper was vacuum dried at 40°C for several hours to obtain the THF-insoluble components such as toner for IR analysis.
[0151] <Confirmation that a specific metal element and a silicon atom are bonded through an oxygen atom> The fact that a specific metal element and a silicon atom are bonded through an oxygen atom was confirmed by IR analysis. As the sample, the THF-insoluble components such as toner obtained by the <Separation method of THF-insoluble components such as toner for IR (infrared spectroscopy) analysis> described above were used. For IR analysis, a Fourier transform infrared spectroscopic analyzer (Frontier: manufactured by PerkinElmer, software: Spectrum10) equipped with a Universal ATR Sampling Accessory is used, and measurement is performed by the ATR method. Hereinafter, the case where the specific metal element is Ti will be described as an example. The absorption peak to be confirmed may be changed according to the specific metal element. The specific measurement procedure is as follows.
[0152] The incident angle of infrared light (λ = 5 μm) is set to 45°. A Ge ATR crystal (refractive index = 4.0) is used as the ATR crystal. Other conditions are as follows. Range Start: 4000cm -1 End: 650cm -1 (ATR crystal of Ge) Duration Scan number: 16 Resolution: 4.00cm -1 Advanced: With CO2 / H2O correction (1) A Ge ATR crystal (refractive index = 4.0) is attached to the device. (2) Set the Scan type to Background and Units to EGY and measure the background. (3) Set Scan type to Sample and Units to A. (4) Accurately weigh 0.01 g of sample and place it on the ATR crystal. (5) Pressurize the sample with the pressure arm (Force Gauge is 45). (6) Measure the sample. Absorption spectrum 926cm -1 Check. 926cm -1 The absorption peak is due to the stretching vibration of the Ti-O-Si bond, and when this peak appears, it is determined that the specific metal element Ti and a silicon atom are bonded via an oxygen atom.
[0153] <Measurement of Water Adsorption Amount of Toner> In the present invention, the "water adsorption amount" of the toner refers to the mass-based water content based on the Karl Fischer method, i.e., the ratio of the water mass to the water-containing toner, and is determined by leaving the toner for 72 hours (3 days) in a normal temperature and normal humidity environment (25°C / 50% RH, N / N environment) and an ultra-high temperature and high humidity environment (32.5°C / 90% RH, hereinafter, SH / H environment) to prepare a sample, and measuring the gas when heated to 125°C based on the Karl Fischer method (JIS K-0068 water evaporation method). EXAMPLES
[0154] The present disclosure will be specifically described with reference to the following examples, which, however, are not intended to limit the present disclosure in any way.
[0155] The toner will be described below. In the examples and comparative examples, "parts" are all by weight unless otherwise specified.
[0156] <Production Example of Toner Base Particle Dispersion> <Production Example of Toner Base Particle Dispersion 1> (Preparation of aqueous medium) 14.0 parts of sodium phosphate (12-hydrate) (manufactured by Rasa Kogyo Co., Ltd.) was added to a reaction vessel containing 385.0 parts of ion-exchanged water, and the mixture was kept at 65°C for 1.0 hour while purging with nitrogen. An aqueous calcium chloride solution in which 9.2 parts of calcium chloride (dihydrate) was dissolved in 10.0 parts of ion-exchanged water was added all at once to the reaction vessel while stirring at 12,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), to prepare an aqueous medium containing a dispersion stabilizer. Furthermore, 1.0 mol / L hydrochloric acid was added to the aqueous medium in the reaction vessel to adjust the pH to 6.0, thereby preparing aqueous medium 1. Aqueous medium 1 contains phosphate ions, which are polyvalent acid ions.
[0157] (Preparation of polymerizable monomer composition (dispersion and dissolution process)) Styrene 60.0 parts CI Pigment Red 122 6.3 parts CI Pigment Red 150 3.7 parts The above materials were placed in an attritor (manufactured by Nippon Coke & Engineering Co., Ltd.), and further dispersed using zirconia particles having a diameter of 1.7 mm at 220 rpm for 5.0 hours to prepare a colorant dispersion in which the pigment was dispersed.
[0158] The following materials were then added to the colorant dispersion: Styrene 10.0 parts 30.0 parts n-butyl acrylate Polyester resin 5.0 parts (condensation polymer of terephthalic acid and 2 moles of propylene oxide adduct of bisphenol A) Fischer-Tropsch wax (melting point 70°C) 7.0 parts The above materials were kept at 65° C. and uniformly dissolved and dispersed at 500 rpm using a TK homomixer to prepare a polymerizable monomer composition.
[0159] (granulation process) While maintaining the temperature of the aqueous medium 1 at 70° C. and the rotation speed of the stirring device at 11,000 rpm, the above polymerizable monomer composition was charged into the aqueous medium 1, and 9.0 parts of t-butyl peroxypivalate as a polymerization initiator was added. Granulation was continued for 10 minutes while maintaining the stirring device at 11,000 rpm.
[0160] (Polymerization step A) The high-speed stirrer was replaced with a stirrer equipped with a propeller stirring blade, and polymerization was carried out for 5.0 hours while stirring at 150 rpm and maintaining the temperature at 70°C.
[0161] (Polymerization step B) Continuing from the polymerization step A, the temperature was further raised to 85° C. and heated for 2.0 hours to carry out the polymerization reaction. Furthermore, 0.018 parts of 3-methacryloxypropyltrimethoxysilane was added. After stirring for 5 minutes, a 1.0 mol / L aqueous solution of sodium hydroxide was added to adjust the pH to 9.0. Furthermore, the temperature was raised to 98° C. and the mixture was heated for 3.0 hours to remove residual monomers. Subsequently, the temperature was lowered to 25° C., and ion-exchanged water was added to adjust the toner base particle concentration in the dispersion to 30% by mass, thereby obtaining toner base particle dispersion 1 in which toner base particles 1 are dispersed. The number average particle diameter (D1) of the toner base particles 1 is 6.1 μm, and the weight average particle diameter (D4) is 6.9 μm. Furthermore, the pH of a portion of the toner base particle dispersion 1 was adjusted to 1.5 with 1.0 mol / L hydrochloric acid, and the mixture was stirred for 1 hour, and then filtered while being washed with ion-exchanged water to obtain toner base particles 1. This was used to measure the silicon ion normalized intensity present on the toner particle surface.
[0162] <Production Example of Toner Base Particle Dispersion Liquid 2> In the manufacturing example of toner base particle dispersion liquid 1, 0.360 parts of 3-methacryloxypropyltrimethoxysilane was added as a material to be added to the colorant dispersion liquid. Furthermore, 3-methacryloxypropyltrimethoxysilane was not added in (polymerization step B). Other than the above, toner base particle dispersion liquid 2 was obtained in the same manner as in the manufacturing example of toner base particle dispersion liquid 1.
[0163] <Production Example of Toner Base Particle Dispersion 3> Toner base particle dispersion liquid 3 was obtained in the same manner as in the production example of toner base particle dispersion liquid 2, except that the amount of 3-methacryloxypropyltrimethoxysilane added was changed to 0.400 parts.
[0164] <Production Examples of Toner Base Particle Dispersions 4 to 8> In the production example of toner base particle dispersion liquid 1, the amount of 3-methacryloxypropyltrimethoxysilane added was changed as shown in Table 1.
[0165] <Production Example of Toner Base Particle Dispersion Liquid 9> In the manufacturing example of the toner base particle dispersion liquid 1, the temperature was lowered to 25° C. in (polymerization step B). Thereafter, the obtained slurry was filtered and reslurried with ion-exchanged water to remove phosphate ions from the slurry. Except for the above, the same procedure as in the production example of toner base particle dispersion liquid 1 was carried out to obtain toner base particle dispersion liquid 9.
[0166] [Table 1] In the table, for example, 1.80.E-02 means 1.80 x 10 -2 This indicates that.
[0167] The symbols (A) and (B) in Table 1 represent the following: (A) Normalized intensity of silicon ions (m / z=28) in a time-of-flight secondary ion mass spectrometer (TOFSIMS) derived from the condensation product of an organosilicon compound in the toner base particles (B) Normalized intensity of silicon ions (m / z=28) after sputtering under the conditions in (A).
[0168] <<Example of manufacturing organosilicon compound liquid>> <Production example of organosilicon compound liquid 1> 70.0 parts of ion-exchanged water Methyltriethoxysilane 30.0 parts The above materials were weighed into a 200 mL beaker, and the pH was adjusted to 3.5 with 10% hydrochloric acid. After that, the mixture was stirred for 1.0 hour while controlling the temperature at 30° C. in a water bath, to prepare organosilicon compound liquid 1.
[0169] <<Example of toner particle production>> <Production Example of Toner Particle 1> 330.0 parts of toner base particle dispersion 1 was weighed out and placed in a reaction vessel, and stirred using a propeller stirring blade. Next, 1.0 mol / L hydrochloric acid was added to adjust the pH of the mixture to 5.5, and immediately thereafter, 5.5 parts of the organosilicon compound liquid 1 were added. Then, 0.50 parts of a 44% aqueous solution of titanium lactate (TC-315: Matsumoto Fine Chemical Co., Ltd., equivalent to 0.22 parts of titanium lactate) was added. Next, the temperature of the mixture was raised to 55°C, and the pH was adjusted to 9.5 over 15 minutes using a 1.0 mol / L NaOH aqueous solution. Thereafter, the temperature was maintained at 55°C for 3 hours while mixing with a propeller stirring blade. After the temperature was lowered to 25° C., the pH was adjusted to 1.5 with 1.0 mol / L hydrochloric acid and stirred for 1 hour, and then the mixture was filtered while being washed with ion-exchanged water to obtain toner particles 1. This was named toner 1. As a result of the analysis, it was confirmed that Toner 1 has a silicon polymer composite containing an organosilicon polymer and titanium atoms on the surface of the toner base particle, and that the silicon polymer composite is fixed to the surface of the toner base particle in a convex shape. It was also confirmed that (ME / SiE) / MX was 1.53 and MX was 0.013. Furthermore, as a result of analyzing the bonding state using infrared spectroscopy, it was confirmed that some of the silicon atoms and titanium atoms are bonded via oxygen atoms.
[0170] <Production Examples of Toner Particles 2 to 12, 18 to 30, and 33> In the production example of toner particle 1, the toner base particle dispersion liquid used and the production conditions were changed as shown in Table 2-1. Otherwise, toner particles 2 to 12, 18 to 30, and 33 were obtained in the same manner as in the production example of toner particle 1. The metal lactates used in toners 10 to 12 are as follows. Zr: Zirconium lactate ammonium salt (Matsumoto Fine Chemical Co., Ltd.) Cu: Copper(II) lactate (n-hydrate) (Mitsuwa Chemical Co., Ltd.) Al: Aluminum L-lactate (Sigma-Aldrich)
[0171] <Production Example of Toner Particle 13> 330.0 parts of toner base particle dispersion 1 was weighed out and placed in a reaction vessel, and stirred using a propeller stirring blade. Next, 1.0 mol / L hydrochloric acid was added to adjust the pH of the mixture to 5.5, and immediately thereafter 0.50 parts of a 44% aqueous solution of titanium lactate (TC-315: manufactured by Matsumoto Fine Chemical Co., Ltd., equivalent to 0.22 parts as titanium lactate) was added. Next, the temperature of the mixture was raised to 55°C, and the pH was quickly adjusted to 9.5 using a 1.0 mol / L NaOH aqueous solution. Then, the mixture was stirred with a propeller agitator while being heated. The temperature was kept at 55° C. for 1 hour. Next, 1.0 mol / L hydrochloric acid was added to adjust the pH of the mixture to 5.5, and immediately thereafter 5.5 parts of the organosilicon compound liquid 1 was added. After that, the pH was adjusted to 9.5 over 15 minutes using a 1.0 mol / L NaOH aqueous solution. The temperature was then maintained at 55°C for 3 hours while mixing using a propeller stirring blade. After lowering the temperature to 25°C, the pH was adjusted to 1.5 with 1.0 mol / L hydrochloric acid and stirred for 1 hour, and then the mixture was washed with ion-exchanged water and filtered to obtain toner particles 13. This was named toner 13. Analysis of the bonding state using infrared spectroscopy confirmed that some of the silicon atoms and titanium atoms were not bonded via oxygen atoms. This is thought to be because titanium lactate reacted with phosphate ions to form titanium phosphate before the silane coupling agent was added, and the reaction was terminated.
[0172] <Production Example of Toner Particle 14> In the production example of toner particle 1, 1 hour after adjusting the pH to 9.5, 0.20 parts of organosilicon compound liquid 1 was further added. In addition, the production conditions were changed as shown in Table 2-1. Otherwise, toner particle 14 was obtained in the same manner as in the production example of toner particle 1.
[0173] <Production Example of Toner Particle 15> In the production example of toner particle 14, the amount of organosilicon compound liquid 1 added was changed to 0.40 parts. In addition, the production conditions were changed as shown in Table 2-1. Otherwise, toner particle 15 was obtained in the same manner as in the production example of toner particle 14.
[0174] <Production Example of Toner Particle 16> In the production example of toner particle 1, one hour after the pH was adjusted to 9.5, an aqueous copper lactate solution was added so that the copper lactate content was 0.02 parts, in addition to the titanium lactate added earlier. Except for this, toner particle 16 was obtained in the same manner as in the production example of toner 1. The copper lactate here was added for the purpose of partially coating the surface of the silicon polymer composite.
[0175] <Production Example of Toner Particle 17> In the production example of toner particle 16, the copper lactate aqueous solution was added so that the amount of copper lactate was 0.03 parts. Except for that, the same procedure as in the production example of toner particle 16 was followed to obtain toner particle 17. Note that the copper lactate was added here for the purpose of partially coating the surface of the silicon polymer composite.
[0176] <Production Example of Toner Particles 31> (Convex formation process) The following samples were weighed and placed in a reaction vessel, and mixed using a propeller agitator. Toner base particle dispersion 1 330.0 parts Organosilicon compound liquid 1 4.5 parts Next, the pH of the resulting mixture was adjusted to 6.0 using a 1 mol / L NaOH aqueous solution, the temperature of the mixture was increased to 50°C, and the mixture was then held for 1.0 hour while being mixed using a propeller agitator (convex formation process 1). Thereafter, the pH of the mixture was adjusted to 9.5 using a 1 mol / L NaOH aqueous solution, and the mixture was maintained for 1.0 hour (protrusion formation step 2).
[0177] (Polyvalent acid metal salt attachment process) Titanium lactate 44% aqueous solution (TC-310: Matsumoto Fine Chemical Co., Ltd.) 0.50 parts (equivalent to 0.22 parts of titanium lactate) · 1.0 parts of organosilicon compound liquid 1 Next, the above sample was weighed and mixed in a reaction vessel, and the pH of the resulting mixture was adjusted to 9.5 using 1 mol / L NaOH aqueous solution and held for 4.0 hours. After lowering the temperature to 25° C., the pH was adjusted to 1.5 with 1 mol / L hydrochloric acid and stirred for 1.0 hour, and then the mixture was washed with ion-exchanged water and filtered to obtain toner particles 31.
[0178] When the cross section of toner particle 31 was observed, protrusions containing an organosilicon polymer and a polyvalent acid metal salt were observed on the surface of the toner base particle, and it was confirmed that titanium was present on the surface of the protrusions, indicating the presence of an organosilicon polymer composite. It was also confirmed that no titanium was present inside the protrusions made of the organosilicon polymer. Furthermore, analysis of the bonding state using infrared spectroscopy confirmed that some of the silicon and titanium atoms were not bonded via oxygen atoms.
[0179] <Production Example of Toner Particles 32> The following samples were weighed and placed in a reaction vessel, and mixed using a propeller agitator. Toner base particle dispersion 1 330.0 parts Organosilicon compound liquid 1 1.0 parts Titanium lactate 44% aqueous solution (TC-310: Matsumoto Fine Chemical Co., Ltd.) 0.46 parts (equivalent to 0.20 parts of titanium lactate) Next, the pH of the resulting mixture was adjusted to 7.0 using a 1 mol / L NaOH aqueous solution, and the temperature of the mixture was increased to 50° C., after which it was held for 1.0 hour while being mixed using a propeller stirring blade. Thereafter, the pH was adjusted to 9.5 using a 1 mol / L NaOH aqueous solution, and the temperature was held at 50° C., while being stirred, for 2.0 hours. While stirring with a propeller impeller, 1.0 mol / L hydrochloric acid was added to adjust the pH of the mixture to 7.0. The following samples were weighed and mixed in the reaction vessel, and then the mixture was held for 1.0 hour. Organosilicon compound liquid 1 4.5 parts The pH was adjusted to 9.5 using a 1 mol / L NaOH aqueous solution, and the temperature was kept at 50° C. for 2.0 hours with stirring. After the temperature was lowered to 25° C., the pH was adjusted to 1.5 using 1 mol / L hydrochloric acid and stirred for 1.0 hour, and then the mixture was washed with ion-exchanged water and filtered to obtain toner particles 32 in which part of the titanium phosphate compound on the surface of the toner base particle 1 is covered with protrusions made of an organosilicon polymer. Analysis of the bond state by infrared spectroscopy confirmed that some of the silicon and titanium atoms were not bonded via oxygen atoms. This is thought to be because titanium lactate reacted with phosphate ions to form titanium phosphate, and the reaction ended before the large amount of organosilicon compound liquid 1 was added in the second stage.
[0180] <Production Example of Toner Particle 34> The toner base particle dispersion 1 was adjusted to pH 1.5 with 1.0 mol / L hydrochloric acid and stirred for 1 hour, and then filtered while being washed with ion-exchanged water. The toner base particles 1 extracted by drying were used as they were as toner particles 34.
[0181] <Toner manufacturing example> <Toner 1-25 Manufacturing Example> Toner particles 1 to 25 were designated as toners 1 to 25, respectively.
[0182] <Production Examples of Comparative Toners 1 to 8> Toner particles 26 to 33 are designated as comparative toners 1 to 8, respectively.
[0183] <Production Example of Comparative Toner 9> Toner particles 34 100.0 parts Titanium oxide particles (volume average particle size 23 nm) 0.028 parts Hydrophobic silica particles surface-treated with dimethyl silicone oil (Volume average particle size of primary particles: 7 nm) 1.00 parts The above materials were charged into a SUPERMIXER PICCOLO SMP-2 (manufactured by Kawata Corporation) and mixed at 3000 rpm for 20 minutes, then sieved through a mesh with 150 μm openings to obtain Comparative Toner 9.
[0184] <Production Example of Comparative Toner 10> Comparative toner 10 was obtained in the same manner as in the preparation example of comparative toner 9, except that the amount of titanium oxide particles added in the preparation example of comparative toner 9 was changed to 0.34 parts.
[0185] The compositions and physical properties of Toners 1 to 25 and Comparative Toners 1 to 10 are shown in Tables 2-1 and 2-2. [Table 2-1] The symbols (A) to (F) in Table 2-1 represent the following: (A) Organosilicon compound liquid volume (parts) (B) Amount of metal lactate solution (parts) (C) Metal lactate amount (parts) (D) Time (min) after adding organosilicon compound solution to add NaOH (E) Temperature of the mixture (℃) (F) pH of the mixture
[0186] [Table 2-2]
[0187] The symbols (G) to (O) in Table 2-2 represent the following: (G) Silicon Polymer Composite (H) Metal atom species contained in silicon polymer composites (I) Metal atom exposure ratio; (ME / SiE) / MX (J) Metal atomic weight relative to silicon atomic weight; MX (K) Presence or absence of a convex shape of the silicon polymer composite. The word "film" indicates that the organosilicon polymer composite does not have a convex shape, but has a film shape. (L) Metal atomic dispersion index; Mmax / Mave (M) Electrical conductivity (S / m) of the silicon polymer composite measured at a frequency of 10 KHz (N) Presence or absence of MO-Si bond (M is a specific metal element) (O) Presence or absence of polyvalent acid metal salts on the toner particle surface
[0188] [Examples 1 to 25, Comparative Examples 1 to 10] The above toners 1 to 25 and comparative toners 1 to 10 were evaluated by the methods described below. The evaluation results are shown in Table 3.
[0189] The evaluation method and evaluation criteria are explained below. <Evaluation machine> The image forming device used was a commercially available laser printer LBP-712Ci (Canon), which was modified to connect to an external high voltage power source and provide an arbitrary potential difference between the charging blade and the charging roller, and the process speed was set to 270 mm / sec. In addition, a commercially available process cartridge, toner cartridge 040H (magenta) (Canon), was used. The product toner was removed from the inside of the cartridge, and after cleaning with an air blower, 165 g of the toner to be evaluated was filled in. The product toner was removed from each of the yellow, cyan, and black stations, and the yellow, cyan, and black cartridges with the toner remaining amount detection mechanism disabled were inserted for evaluation.
[0190] <Evaluation of fogging> First, the main body and cartridge were left in an ultra-high temperature and high humidity environment (32.5°C / 90% RH, hereinafter referred to as SH / H environment) for 5 days. After leaving them, the following evaluations were carried out. The development conditions were set to a charging blade voltage of -500 V and a developing roller voltage of -300 V. In a SH / H environment, a printout test of 30,000 sheets in total was performed by repeating intermittent operation in which the printout was stopped once every two sheets of an image with a print rate of 1%. After the printout test was completed, a solid white image was output, and the reflectance (%) of the solid white image was measured using a REFLECTOMETER MODEL TC-6DS (manufactured by Tokyo Denshoku Co., Ltd.). The reflectance obtained was subtracted from the reflectance (%) of unused printout paper (standard glossy paper) measured in the same manner, and the result was used for evaluation. The smaller the value, the more suppressed the image fog. A solid white image was output in glossy paper mode using glossy paper (HP Brochure Paper 200g, Glossy, manufactured by HP, 200g / m 2 The evaluation was carried out before and after the 30,000 sheets were printed. A grade of C or higher was judged to be good.
[0191] A toner having excellent electrostatic properties can provide a good image with little fog. Toners with excellent environmental stability and low moisture absorption of the surface layer exhibit good chargeability even in high humidity environments. Toners with little fog can reduce toner consumption during long-term use, thereby increasing the number of pages that can be printed with a toner cartridge. (Evaluation Criteria) A: The deduction is less than 0.4% B: The deduction is between 0.4% and 0.8% C: The deduction is between 0.8% and 1.3%. D: The subtracted value is 1.3% or more.
[0192] Furthermore, the above-mentioned evaluation of fog was also carried out in a low temperature and low humidity environment (15° C. / 10% RH, hereinafter referred to as LL environment). Furthermore, the process speed was changed to 230 mm / sec, and the test was also performed in a high temperature and high humidity environment (32.5°C, humidity 80% RH, hereafter referred to as H / H environment).
[0193] <Contactability> The development conditions were set as follows: the charging blade voltage was -500 V, and the developing roller voltage was -300 V. Using the above process cartridge and the above modified laser printer, a LETTER size Business 4200 paper (XEROX, 75 g / m 2 ) five solid images were printed. The solid image was evaluated for its solid followability. The image density was measured using a Macbeth Reflection Densitometer RD918 (Macbeth) according to the attached instruction manual, by measuring the relative density of the image to the white background part where the image density is 0.00, and the obtained relative density was regarded as the image density value. Note that C or higher was judged to be a good level. (Evaluation criteria for solid color conformity) The evaluation was made based on the difference in image density between the leading edge of the first all-solid image and the trailing edge of the third all-solid image. A: The difference between the image density at the leading edge of the first full solid image and the image density at the trailing edge of the third full solid image is less than 0.10. B: The difference between the image density of the leading edge of the first solid image and the image density of the trailing edge of the third solid image is 0.10 or more and less than 0.20 C: The difference between the image density of the leading edge of the first all-solid image and the image density of the trailing edge of the third all-solid image is 0.20 or more and less than 0.30 D: The difference between the image density of the leading edge of the first solid image and the image density of the trailing edge of the third solid image is 0.30 or more.
[0194] <Evaluation of transfer efficiency> The transfer efficiency is an index of transferability that indicates what percentage of the toner developed on the photosensitive drum is transferred onto the intermediate transfer belt. The development conditions were set at a charging blade voltage of -500 V and a developing roller voltage of -300 V. The transfer efficiency was evaluated using the modified laser printer described above (process speed: 270 mm / sec) and a LETTER size Business 4200 paper (Xerox, 75 g / m 2 ) was used to form a full solid image on the recording medium. The primary transfer bias of the modified laser printer was set to a potential that was 100 V lower than the normal potential, and the full solid image was output in an ultra-high temperature and high humidity environment (32.5°C / 90% RH, SH / H environment). After that, the toner transferred onto the intermediate transfer belt and the toner remaining on the photosensitive drum after transfer were peeled off with a transparent polyester adhesive tape. The toner density difference was calculated by subtracting the density when only the adhesive tape was stuck to the paper from the toner density when the peeled adhesive tape was stuck to the paper. The transfer efficiency is the ratio of the toner density difference on the intermediate transfer belt when the sum of the toner density differences is set to 100, and the higher this ratio, the better the transfer efficiency. The transfer efficiency was evaluated according to the following criteria. A grade of C or higher was considered to be a good level. The toner concentration was measured using an X-Rite color reflection densitometer (500 series). A: Transfer efficiency is 98% or more B: Transfer efficiency is 95% or more but less than 98% C: Transfer efficiency is 90% or more but less than 95% D: Transfer efficiency is less than 90%
[0195] <Evaluation of water adsorption amount> The amount of moisture adsorption was calculated using the method described above, and the difference between the NN and SHH environments was calculated.
[0196] [Table 3]
[0197] The present disclosure relates to the following configurations. (Configuration 1) A toner having toner particles having a binder resin, The toner particles have a toner base particle and a silicon polymer composite present on a surface of the toner base particle, The silicon polymer composite comprises: a silicon polymer; At least one specific metal atom selected from the group consisting of metal atoms included in Groups 3 to 13; Contains a ratio of the number of specific metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, phosphorus atoms and the specific metal atoms, which is obtained by X-ray photoelectron spectroscopy analysis of the toner, is defined as ME, and a ratio of the number of silicon atoms is defined as SiE, In an EDS mapping image of constituent elements of a cross section of the toner, which is obtained by analyzing the cross section of the toner observed with a transmission electron microscope with an energy dispersive X-ray spectrometer, the ratio of the number of atoms of the specific metal atoms to the sum of the numbers of silicon atoms and the specific metal atoms in a region outside the contour of the toner mother particle is defined as MX, The ME, the SiE, and the MX satisfy the following formulas (1) and (2): 0.50 ≦(ME / SiE) / MX ≦ 2.50 (1) 5.0×10 -3 ≦MX ≦6.0×10 -2 (2) A toner characterized by: (Configuration 2) The toner according to configuration 1, wherein MX satisfies the following formula (3): 1.0×10 -2 ≦MX ≦6.0×10 -2 (3) (Configuration 3) 3. The toner according to configuration 1 or 2, wherein the silicon polymer composite is fixed to the surface of the toner base particle in a convex shape. (Configuration 4) an image of the toner base particle and an image of the silicon polymer composite are observed in the EDS mapping image, and the image of the silicon polymer composite is observed at a position in the image of the toner base particle that corresponds to a surface of the toner base particle; In the EDS mapping image, when a line scan is performed on an area X specified by the following method, the maximum value of the intensity count of the specific metal atom is Mmax and the average value of the intensity count is Mave, The toner according to configuration 3, wherein the Mmax and the Mave satisfy the following formula (4): 1.00 <Mmax / Mave<1.80 ···(4); How to identify Region X: (i) connecting the end points of the interface formed by the silicon polymer composite image and the toner base particle image with a straight line to define a baseline; (ii) determining a perpendicular line L1 having the maximum length among perpendicular lines connecting the base line and the outer surface of the image of the silicon polymer composite; (iii) When the width of the image of the silicon polymer composite, which is the length of the baseline, is W, a line segment L2 is defined on the baseline by connecting two points on the baseline that are 0.1W inward from each end of the baseline. (iv) The area where the line segment L2 is moved parallel to the base line in the direction in which the perpendicular line L1 extends to the midpoint of the perpendicular line L1 and the image of the silicon polymer composite overlaps is defined as "area X." (Configuration 5) The electrical conductivity of the silicon polymer composite measured at a frequency of 10 kHz is 1.0×10 -5 ~1.0×10 -2 5. The toner according to any one of configurations 1 to 4, wherein S / m. (Configuration 6) 6. The toner according to any one of Configurations 1 to 5, wherein in the silicon polymer composite, at least a portion of the specific metal atoms and at least a portion of the silicon atoms are bonded via an oxygen atom. (Configuration 7) The toner according to any one of configurations 1 to 6, wherein the specific metal atom includes at least one metal atom selected from the group consisting of titanium, zirconium, copper, and aluminum. (Configuration 8) The toner according to any one of configurations 1 to 7, wherein the specific metal atom includes titanium. (Configuration 9) The toner according to any one of configurations 1 to 8, wherein the silicon polymer composite contains a polyvalent acid metal salt containing a metal atom and a polyvalent acid. (Configuration 10) the toner base particles contain a condensation product of an organosilicon compound, The normalized intensity of the silicon ion (m / z=28) represented by the following formula (I) derived from the condensation product in a time-of-flight secondary ion mass spectrometry TOF-SIMS of the toner base particles is 7.00×10 -4 ~3.00×10 -2 and Normalized silicon ion intensity (m / z=28)={ion intensity of silicon ion (m / z=28)} / {total ion intensity from m / z=0.5 to 1850} (I) The toner base particles are sputtered by an Ar gas cluster ion beam Ar-GCIB under the following condition (A), and then the normalized intensity of the silicon ion (m / z=28) measured by the time-of-flight secondary ion mass spectrometry is 6.99×10 -4 Below is the The toner according to any one of Configurations 1 to 9. (A) Conditions Acceleration voltage: 5 kV, current: 6.5 nA, raster size: 600 × 600 μm, irradiation time: 5 sec / cycle, sputtering time: 250 sec [Explanation of symbols]
[0198] 1. Silicon polymer composite; 2. Toner base particle; 3. Line segment connecting the endpoints of the interface formed by the image of the silicon polymer composite and the image of the toner base particle; 4. Range from the outer edge of the cross section of the silicon polymer to the center parallel to the base line and inside 0.1W; 5. Perpendicular line that has the longest length among the perpendicular lines connecting the base line and the surface of the image of the silicon polymer.
Claims
1. A toner having toner particles having a binder resin, The toner particles have a toner base particle and a silicon polymer composite present on a surface of the toner base particle, The silicon polymer composite comprises: a silicon polymer; At least one specific metal atom selected from the group consisting of metal atoms included in Groups 3 to 13; Contains a ratio of the number of specific metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, phosphorus atoms and the specific metal atoms, which is obtained by X-ray photoelectron spectroscopy analysis of the toner, is defined as ME, and a ratio of the number of silicon atoms is defined as SiE, In an EDS mapping image of constituent elements of a cross section of the toner, which is obtained by analyzing the cross section of the toner observed with a transmission electron microscope with an energy dispersive X-ray spectrometer, the ratio of the number of atoms of the specific metal atoms to the sum of the numbers of silicon atoms and the specific metal atoms in a region outside the contour of the toner mother particle is defined as MX, The ME, the SiE, and the MX satisfy the following formulas (1) and (2): 0.50≦(ME / SiE) / MX≦2.50...(1) 5.0×10 -3 ≦ MX ≦6.0×10 -2 ・・・(2) A toner characterized by:
2. The toner according to claim 1 , wherein the MX satisfies the following formula (3): 1.0×10 -2 ≦ MX ≦6.0×10 -2 ・・・(3)
3. 2. The toner according to claim 1, wherein the silicon polymer composite is adhered to the surface of the toner base particle in a convex shape.
4. an image of the toner base particle and an image of the silicon polymer composite are observed in the EDS mapping image, and the image of the silicon polymer composite is observed at a position in the image of the toner base particle that corresponds to a surface of the toner base particle; In the EDS mapping image, when a line scan is performed on an area X specified by the following method, the maximum value of the intensity count of the specific metal atom is defined as Mmax and the average value of the intensity count is defined as Mave, The toner according to claim 3 , wherein the Mmax and the Mave satisfy the following formula (4): 1.00<Mmax / Mave<1.80...(4); How to identify region X: (i) connecting the end points of the interface formed by the silicon polymer composite image and the toner base particle image with a straight line to define a baseline; (ii) determining a perpendicular line L1 having the maximum length among perpendicular lines connecting the base line and the outer surface of the image of the silicon polymer composite; (iii) when the width of the image of the silicon polymer composite, which is the length of the baseline, is W, a line segment L2 is defined by connecting two points on the baseline that are 0.1W inward from each end of the baseline. (iv) The line segment L2 is moved parallel to the base line in the direction in which the perpendicular line L1 extends to the position of the midpoint of the perpendicular line L1, and the area where the moved line segment overlaps with the image of the silicon polymer composite is defined as "area X".
5. The electrical conductivity of the silicon polymer composite measured at a frequency of 10 kHz is 1.0×10 -5 ~1.0 x 10 -2 The toner according to any one of claims 1 to 4, wherein the toner has a molecular weight of S / m.
6. 5. The toner according to claim 1, wherein in said silicon polymer composite, at least a portion of said specific metal atoms and at least a portion of said silicon atoms are bonded via an oxygen atom.
7. 5. The toner according to claim 1, wherein the specific metal atom comprises at least one metal atom selected from the group consisting of titanium, zirconium, copper and aluminum.
8. 5. The toner according to claim 1, wherein the specific metal atom includes titanium.
9. 5. The toner according to claim 1, wherein the silicon polymer composite comprises a polyvalent acid metal salt comprising a metal atom and a polyvalent acid.
10. the toner base particles contain a condensation product of an organosilicon compound, The normalized intensity of the silicon ion (m / z=28) represented by the following formula (I) derived from the condensation product in the time-of-flight secondary ion mass spectrometry TOF-SIMS of the toner base particles is 7.00×10 -4 ~3.00 x 10 -2 and Normalized silicon ion intensity (m / z=28)={ionic intensity of silicon ion (m / z=28)} / {total ionic intensity at m / z=0.5 to 1850} (I) The toner base particles are sputtered by an Ar gas cluster ion beam (Ar-GCIB) under the following condition (A), and then the normalized intensity of the silicon ion (m / z=28) measured by the time-of-flight secondary ion mass spectrometry is 6.99×10 -4 Below is the The toner according to any one of claims 1 to 4. (A) Conditions Acceleration voltage: 5 kV, current: 6.5 nA, raster size: 600×600 μm, irradiation time: 5 sec / cycle, sputtering time: 250 sec
Citation Information
Patent Citations
Toner for non-magnetic one-component supplying system electrophotography
JP2007017486A
Toner
JP2011118210A
Toner
JP2021021791A